Process cartridge and electrophotographic apparatus

JP7638647B2Active Publication Date: 2025-03-04CANON KK
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2020155391
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-18
Filing Date
2020-09-16
Publication Date
2025-03-04
Estimated Expiration
2040-09-16

AI Technical Summary

Benefits of technology

【0015】 本発明の一態様によれば、良好な電位変動を維持しつつ、横走りを抑制し得るプロセスカートリッジを得ることができる。また、本発明の他の態様によれば、高品位な電子写真画像を形成することができる電子写真装置を得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007638647000018
    Figure 0007638647000018
  • Figure 0007638647000019
    Figure 0007638647000019
  • Figure 0007638647000020
    Figure 0007638647000020
Patent Text Reader

Abstract

To provide a process cartridge that prevents lateral running while maintaining a good potential variation.SOLUTION: A process cartridge has an electrophotographic photoreceptor having a first support, an undermost layer, and a photosensitive layer, and an electrifying member having a second support and a second conductive layer. The second conductive layer has a matrix and domains including a second rubber and an electronic conductive agent. The volume resistivity of the matrix ρM is 1.0×105 or more times the volume resistivity of the domains ρD. When an AC voltage is applied to the undermost layer while changing the voltage to measure an impedance, the maximum frequency at which the phase of the impedance becomes 45° is fOPC Hz, and when an AC voltage is applied to the electrifying member while changing the voltage to measure an impedance, the maximum frequency at which the phase of the impedance becomes 45° is fC Hz, fOPC and fC are values within constant ranges.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a process cartridge and an electrophotographic apparatus having an electrophotographic photosensitive member and a charging member. [Background technology]

[0002] The electrophotographic process related to electrophotographic photoreceptors (hereinafter simply referred to as "photoreceptors") mainly consists of four processes: charging, exposure, development, and transfer, with additional processes such as cleaning and pre-exposure added as necessary. Among these, the charging process and exposure process are the key processes for electrostatic latent image formation, which control the charge distribution of the photoreceptor and make the photoreceptor surface have the desired potential distribution. The charging process generates discharge from the charging member (charging means) to the electrophotographic photoreceptor, charging the photoreceptor surface. In this case, if the electrical characteristics of the photoreceptor and the charging member and the frequency dependence of the electrical characteristics are not properly designed, excessive discharge can cause the photoreceptor to break down (hereinafter also referred to as "leak"), or poor charging can occur due to unstable discharge, which can be problematic. For this reason, a layer with controlled resistance (hereinafter referred to as the "bottom layer") has been provided directly above the support of the photoreceptor, in addition to the photosensitive layer, to electrically conceal unevenness caused by burrs on the surface of the support, thereby suppressing leaks and poor charging.

[0003] When considering the photoconductor characteristics from the viewpoint of electrical resistance, it is desirable for the electrical resistance to be high in order to suppress leakage and improve charging ability to suppress charging defects, but if the electrical resistance is made too high, the light sensitivity will deteriorate in the exposure process. In particular, when repeatedly printing images using a photoconductor with high electrical resistance, the charge does not easily escape, and the charge accumulates inside the photoconductor over a long period of use. As a result, the bright area potential gradually increases (hereinafter also referred to as "potential fluctuation"), and the contrast with the dark area potential decreases. Therefore, when considering the exposure process, it is preferable for the photoconductor to have low electrical resistance.

[0004] Therefore, conventionally, the electrical characteristics of the bottom layer and photoconductor have been designed based on the concept of impedance, and the electrical characteristics have been optimized taking into account frequency dependency.By doing so, the above-mentioned problem has been addressed by optimizing the electrical characteristics in the frequency bands corresponding to the respective time constants for the characteristic time scales that differ for each electrophotographic process, such as the charging process and the exposure process, in accordance with the process.

[0005] On the other hand, corona type and roller type have been mainly used as charging members that impart charge to the photoreceptor during the charging process. Of these, corona type requires a higher applied voltage than roller type, which poses problems in terms of the size and cost of the power supply required. On the other hand, roller type requires a lower applied voltage, which allows the size and cost of the power supply to be kept small. However, roller type has a problem in that it is inferior to corona type in terms of uniformity and stability of charging.

[0006] In addition, in the case of a roller-type charging member (hereinafter also referred to as a "charging roller"), the charging roller and the photoconductor are in direct contact with each other, so that the photoconductor is locally scratched down to the lowest layer surface or has holes due to the intrusion of foreign matter into the photosensitive layer or dents caused by impact, and the voltage applied to the photoconductor in that local area is largely divided to the lowest layer. In such a case, a large current flows from the surface side of the photoconductor to the support side through that area. This causes a shortage of charge supply to the charging roller, and discharge to the photoconductor surface is not sufficiently performed, resulting in linear charging failure in the longitudinal direction of the charging roller. When an image is printed in this state, an image with black lines drawn in the longitudinal direction of the photoconductor (hereinafter referred to as a "horizontal running image") is output. This phenomenon (hereinafter referred to as "horizontal running") was a problem because it was difficult to completely control the intrusion of foreign matter or the occurrence of dents caused by impact.

[0007] Patent Document 1 describes a photoreceptor having a photosensitive layer containing a photoconductive material on an aluminum substrate having an aluminum oxide coating on its surface. By controlling the impedance of the aluminum oxide coating, fogging due to localized charging defects is suppressed.

[0008] In Patent Document 2, the angular frequency ω max [rad] is 2≦ω max The document describes a photoreceptor having an undercoat layer in which the impedance is ≦10. By controlling the impedance of the undercoat layer within the above-mentioned range, the occurrence of abnormal discharge caused by excessive charge movement in the undercoat layer during the charging process is suppressed, and streak-like image quality defects in images with low image density are suppressed.

[0009] In Patent Document 3, the volume resistivity is 1×10 12 The document describes a rubber composition with an islands-in-a-sea structure that includes a polymer continuous phase made of an ionically conductive rubber material mainly composed of raw rubber A having a resistance of Ω·cm or less, and a polymer particle phase made of an electronically conductive rubber material made conductive by blending conductive particles into raw rubber B, and an electrostatic charging member having an elastic layer formed from the rubber composition. The islands-in-a-sea structure of the ionically conductive rubber material and the electronically conductive rubber material provides the electrostatic charging member with excellent resistance stability. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] Japanese Patent Application Publication No. 10-268541 [Patent Document 2] JP 2016-139052 A [Patent Document 3] JP 2002-3651 A Summary of the Invention [Problem to be solved by the invention]

[0011] According to the inventors' investigations, it was difficult to suppress lateral movement while maintaining favorable potential fluctuation in the electrophotographic photoreceptors and charging members described in Patent Documents 1 to 3.

[0012] According to one aspect of the present invention, there is provided a process cartridge capable of suppressing lateral movement while maintaining favorable potential fluctuation. Another aspect of the present invention is to provide an electrophotographic apparatus capable of forming a high-quality electrophotographic image. [Means for solving the problem]

[0013] According to one aspect of the present invention, there is provided a process cartridge having an electrophotographic photosensitive member and a charging member, and being detachably mountable to a main body of an electrophotographic apparatus, the electrophotographic photosensitive member being an electrophotographic photosensitive member having a cylindrical first support, a bottom layer formed directly on the first support, and a photosensitive layer formed on the bottom layer, A needle electrode having a diameter of 1 mm connected to the high voltage side of an impedance measuring device was brought into contact with the first support, and the earth side conductor of the impedance measuring device was connected to the first support. A DC voltage of -8 V was applied to the surface of the first support with an amplitude of 1 Vpp. AC voltage with frequency 1.0 x 10 -2 [Hz]-1.0×10 6 When the impedance is measured while changing the frequency between f [Hz], the maximum frequency at which the phase of the impedance is 45° is called f OPC [Hz], the charging member is an electrophotographic charging member having a cylindrical second support and a second conductive layer formed on the second support, the second conductive layer having a matrix containing a first rubber and a plurality of domains dispersed in the matrix, the domains containing a second rubber and an electronic conductive agent, and the volume resistivity ρ of the matrix is M is the volume resistivity ρ of the domain D 1.0 x 10 5 times or more, A strip-shaped metal thin film electrode having a longitudinal width of 1.5 cm is provided in the circumferential direction on the surface of the substrate, and the metal thin film electrode is connected to one end of an impedance measuring device, and the second support is connected to the other end of the impedance measuring device. AC voltage with frequency 1.0 x 10 -2 [Hz]-1.0×10 6 When the impedance is measured while changing the frequency between f [Hz], the maximum frequency at which the phase of the impedance is 45° is called f C [Hz], f OPC and f C satisfies the relationship of the following formula (D1) or the following formula (D2): 10≦f OPC / f C ≦10,000 Formula (D1) 0.0001≦f OPC / fC ≦0.1 Equation (D2).

[0014] According to another aspect of the present invention, there is provided an electrophotographic apparatus having an electrophotographic photosensitive member and a charging member, the electrophotographic photosensitive member having a cylindrical first support, a bottom layer formed directly on the first support, and a photosensitive layer formed on the bottom layer, A needle electrode having a diameter of 1 mm connected to the high voltage side of an impedance measuring device was placed in contact with the surface of the first support, and the exposed core material of the first support was connected to the earth side of the impedance measuring device. A DC voltage of -8 V with an amplitude of 1 Vpp was applied to the surface of the first support. AC voltage with frequency 1.0 x 10 -2 [Hz]-1.0×10 6 When the impedance is measured while changing the frequency between f [Hz], the maximum frequency at which the phase of the impedance is 45° is called f OPC [Hz], the charging member is an electrophotographic charging member having a cylindrical second support and a second conductive layer formed on the second support, the second conductive layer having a matrix containing a first rubber and a plurality of domains dispersed in the matrix, the domains containing a second rubber and an electronic conductive agent, and the volume resistivity ρ of the matrix is M is the volume resistivity ρ of the domain D 1.0 x 10 5 times or more, A thin metal film electrode is provided on the surface of the support, a metal sheet is wrapped around the thin metal film electrode, the metal sheet is connected to the high voltage side electrode of an impedance measuring device, and the second support is connected to the earth side of the impedance measuring device. AC voltage with frequency 1.0 x 10 -2 [Hz]-1.0×10 6 When the impedance is measured while changing the frequency between f [Hz], the maximum frequency at which the phase of the impedance is 45° is called f C [Hz], f OPC and f C satisfies the relationship of the following formula (D1) or the following formula (D2): 10≦f OPC / f C ≦10,000 Formula (D1) 0.0001≦f OPC / f C ≦0.1 Equation (D2). Effect of the Invention

[0015] According to one aspect of the present invention, it is possible to obtain a process cartridge capable of suppressing lateral movement while maintaining favorable potential fluctuation, and according to another aspect of the present invention, it is possible to obtain an electrophotographic apparatus capable of forming a high-quality electrophotographic image. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is a diagram showing an example of a schematic configuration of an electrophotographic apparatus having a process cartridge including an electrophotographic photosensitive member and a charging member. [Diagram 2] 1 is a schematic diagram of a sea-island structure of the charging member of the present invention. [Diagram 3] FIG. 2 is an explanatory diagram of impedance characteristics required in the present invention. [Figure 4] FIG. 13 is an explanatory diagram of impedance characteristics in Example 5 of the present invention. [Diagram 5] FIG. 13 is an explanatory diagram of impedance characteristics in Example 7 of the present invention. [Figure 6] FIG. 11 is an explanatory diagram of impedance characteristics in Comparative Example 4 of the present invention. [Figure 7] FIG. 4 is an explanatory diagram of impedance characteristics in Comparative Example 1 of the present invention. [Figure 8] FIG. 11 is an explanatory diagram of impedance characteristics in Comparative Example 6 of the present invention. [Figure 9] FIG. 21 is an explanatory diagram of impedance characteristics in Example 17 of the present invention. [Figure 10] FIG. 2 is a schematic diagram of a charging roller produced in an example in which a measurement electrode is formed. [Figure 11] FIG. 4 is a cross-sectional view of a charging roller having a measurement electrode formed thereon. [Figure 12] FIG. 1 is a schematic diagram of an impedance measurement system. [Figure 13] 5A to 5C are explanatory diagrams of a method for manufacturing the charging member. [Figure 14] FIG. 1 is a schematic diagram of a leak test device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The present invention will be described in detail below with reference to preferred embodiments. As a result of the inventors' investigations, it was found that simply optimizing the impedance of the aluminum oxide coating or undercoat layer in conventional photoreceptors does not have the effect of suppressing the above-mentioned foreign matter contamination and lateral movement due to dents while maintaining good potential fluctuations. Therefore, the inventors discovered that in order to optimize the combination of the photoconductor and the charging member and solve the above problems, the photoconductor and the charging member are designed as follows, and the combination is further optimized, thereby making it possible to suppress lateral movement while maintaining favorable potential fluctuation.

[0018] <Photoreceptor design> The inventors have found that the photoreceptor needs to have a bottom layer on a cylindrical support (hereinafter, the support of the photoreceptor is referred to as the "first support") This bottom layer plays a role in preventing the first support from being completely exposed in the event that the photoreceptor is contaminated with foreign matter or is dented.

[0019] <Design of electrostatically charged components> The inventors also discovered that the electrostatic charging member is a charging member having a conductive layer (hereinafter, the conductive layer of the electrostatic charging member will be referred to as the "second conductive layer") formed on a cylindrical support (hereinafter, the support of the electrostatic charging member will be referred to as the "second support"), that the second conductive layer has a sea-island structure (see Figure 2), and that the sea portion must have a certain level of resistance or higher compared to the island portions.

[0020] Here, the "sea-island structure" of the second conductive layer is a structure having a matrix 6a, which is a sea portion containing a first rubber, and domains 6b, which are a plurality of island portions dispersed in the matrix 6a, and the domains 6b contain a second rubber and an electronic conductive agent 6c, as shown in Fig. 2. In addition, "the sea portion has a certain level of resistance compared to the island portions" specifically means, for example, that the volume resistivity ρ M [Ω cm] and the volume resistivity ρ of domain 6b D Ratio ρ of [Ω cm] M / ρ D But 1.0×10 5 That's all.

[0021] <Optimizing the combination of photoconductor and charging member> In the present invention, when combining a photoconductor and a charging member, it is necessary to separate the reaction frequency of the photoconductor and the reaction frequency of the charging member by a certain amount or more, but not by a limit value or more.

[0022] The "reaction frequency" referred to here is the frequency of AC voltage applied to the photoconductor or charging member at a frequency of 1.0 x 10 -2 [Hz]~1.0×10 6 When the impedance is measured while changing the frequency between f [Hz] and f [Hz], the maximum frequency at which the phase of the impedance is 45° is defined as the response frequency of the photoconductor. OPC [Hz], the reaction frequency of the charged member is f C In addition, "separated by a certain amount" means that the ratio of the reaction frequency of the photoconductor to the reaction frequency of the charging member is one digit or more, that is, f OPC / f C This means that the photoconductor response frequency f OPC and the reaction frequency of the charged member f C The ratio of f is four digits or less. OPC / f C This means that f is less than or equal to 10,000 or greater than or equal to 0.0001. OPC / f C satisfies the relationship of the following formula (D1) or the following formula (D2). 10≦f OPC / f C ≦10,000 Formula (D1) 0.0001≦f OPC / f C ≦0.1 Formula (D2)

[0023] Figures 4, 5, 6, 7, 8, and 9 show the impedance measurement results of the bottom layer of the photoconductor and the charging member in the configurations of the examples of the present invention and the comparative examples. Figures 4, 5, and 6 show the impedance measurement results when the bottom layer is changed for the same charging member. In Figures 4 and 5, the response frequency fOPC and the reaction frequency of the charged member f C The effect of the present invention is realized because the response frequency f of the lowest layer in FIG. OPC and the reaction frequency of the charged member f C 7, 8, and 9 show the impedance measurement results when the charging members in Figs. 4, 5, and 6 are changed. OPC and the reaction frequency of the charged member f C In Figure 9, the two reaction frequencies are too far apart, so the effect of the present invention is not achieved, and in Figure 8, the two reaction frequencies are too close, so the effect of the present invention is not achieved. On the other hand, in Figure 9, the ratio of the two reaction frequencies is within the required range, so the effect of the present invention is achieved.

[0024] The relationship between impedance and reaction frequency will be explained below. When measuring the impedance of a sample, the equivalent circuit can be roughly expressed as a parallel circuit (hereinafter also referred to as an "RC parallel circuit") consisting of the electrical resistance R [Ω], which is the resistance component, and the electrostatic capacitance C [Ω], which is the capacitance component. The impedance Z [Ω] and absolute value of the impedance |Z| [Ω] of the sample at this time are expressed by the following formulas (E1) and (E2), respectively.

number

number

[0025] Moreover, when considering the polar coordinate representation of Z, Z can be expressed by the following equation (E3) using the phase θ.

number

number

[0026] FIG. 3 shows the f-θ graph of formula (E4). In the case of the RC parallel circuit model shown here, R and C are constants specific to each sample, so when θ=0°, f=0. At this time, the impedance is dominated by the resistance component. On the other hand, when θ=90°, f→∞, and the impedance is dominated by the capacitance component. When θ=45°, the RC parallel circuit is in a transitional period of two components, resistance R and capacitance C, and is highly reactive. In the present invention, the frequency corresponding to θ=45° is called the reaction frequency. Here, "high reactivity" refers to a characteristic in which, for example, when a locally low-resistance part caused by a conductive foreign object piercing or hitting the surface of the photoconductor enters the charging process section and the shared voltage applied to the photoconductor changes suddenly, a large electrical load is applied to the charging member or photoconductor due to the sudden change in the shared voltage.

[0027] The inventors speculate as follows why the combination of the photoconductor and the charging member is effective in suppressing lateral movement while maintaining favorable potential fluctuation.

[0028] First, the photoconductor has a bottom layer, which prevents the first support from being completely exposed even if the photoconductor layer is locally damaged by a conductive foreign object piercing or being struck. Therefore, the bottom layer can stop the large current that occurs between the first support of the photoconductor and the charging roller through the locally damaged area during the charging process, thereby preventing lateral movement.

[0029] Secondly, the second conductive layer has a sea-island structure in which the matrix has a certain level of resistance compared to the domains, so that in the charging process, discharge onto the photoconductor surface mainly occurs from the domains. Moreover, because the discharges in multiple domains are electrically isolated by the matrix, the discharges are prevented from combining and growing. This prevents a large current from flowing into a localized area of ​​the photoconductor, even if the electrical resistance is reduced due to localized damage to the photoconductor. As a result, insufficient discharge onto the photoconductor surface due to insufficient charge supply to the charging roller is suppressed, and linear charging defects along the length of the charging roller, i.e., lateral running, are suppressed.

[0030] Third, the photoconductor response frequency f OPC and the reaction frequency of the charged member f C By separating them by a certain amount or more, it is possible to prevent the photoconductor and charging member from being subjected to a large electrical load simultaneously with the same time constant during the charging process. When the surface of the photoconductor approaches the contact point with the charging roller (hereinafter also referred to as the "nip") as the charging roller rotates, a discharge occurs in a tiny gap near the nip. When a locally low-resistance portion caused by a conductive foreign object piercing or hitting the photoconductor surface enters, a large current is likely to occur suddenly on the photoconductor surface, while the shared voltage is likely to increase suddenly on the surface of the charging member corresponding to the low-resistance portion. Therefore, the reaction frequency f of the photoconductor OPC and the charging roller response frequency f C The inventors believe that if the photoconductor response frequency f is close to the photoconductor response frequency f, the electrical loads on both the photoconductors will be large at the same time, and there is a high possibility that a large current will be generated. OPC and the charging roller response frequency f C By separating them by a certain amount, it is possible to prevent a large current from flowing between the charging roller and the photoconductor, thereby suppressing lateral movement.

[0031] On the other hand, f OPC and f CBy not separating them more than the limit value, the impedance characteristics such as the electrical resistance and capacitance of the photoconductor when the charging member is discharging during the charging process change to some extent. As a result, various memories accumulated in the photoconductor by the previous processes such as exposure and transfer are alleviated, high-quality charging is performed through uniform and stable discharge, and good image quality can be maintained.

[0032] As shown above, the lateral movement is controlled not by the electrical resistance of the bottom layer of the photoconductor or the second conductive layer of the charging member, but by optimizing the combination of the reaction frequencies of the photoconductor and the charging member, so it becomes easier to independently control the electrical resistance to achieve good potential fluctuation. Also, as per the mechanism described above, the memory in the photoconductor is mitigated and high-quality charging is performed, which also contributes to the achievement of good potential fluctuation.

[0033] [Electrophotographic photoreceptor] The electrophotographic photoreceptor according to the present invention is characterized by having a bottom layer and a photosensitive layer formed on the bottom layer. Here, the bottom layer means a surface treatment layer, undercoat layer, or conductive layer (hereinafter, the conductive layer of the electrophotographic photoreceptor is also referred to as the "first conductive layer") formed by performing electrochemical treatment or the like on the surface of the first support, which is laminated directly on the first support. The surface treatment layer and the first conductive layer on the surface of the first support will be described later. The material constituting the bottom layer is preferably an inorganic substance from the viewpoint of deterioration due to long-term use.

[0034] f when measuring the impedance of the bottom layer OPC [Hz] is preferably 5 [Hz] or more, and particularly preferably 100 [Hz] or more. OPC By increasing the discharge amount per discharge, the number of discharges can be increased while reducing the discharge amount per discharge, improving both lateral movement and potential fluctuation.

[0035] Also, f OPC Impedance z per unit area of ​​the bottom layer at / 10[Hz] OPC is 3.0 x 10 5 [Ω cm 2] or more, and more preferably 1.0 × 10 9 [Ω cm 2 ] or less is more preferable.

[0036] f OPC and z OPC is controlled by various parameters such as the material of the resin constituting the bottom layer, the metal oxide and the surface treatment of the metal oxide, the film thickness, the mixture ratio and dispersion state of the resin and the metal oxide. For example, f OPC can be controlled by the time constant τ = RC. Here, R is the resistance of the bottom layer, and C is the capacitance of the bottom layer. In general, when R is increased, the phase change region in impedance measurement shifts to the low frequency side, so f OPC The same effect can be obtained by increasing C.

[0037] As a method for producing such an electrophotographic photoreceptor, a method of preparing a coating liquid for each layer described later, coating the layers in the desired order, and drying the liquid can be mentioned. In this case, as a method for coating the coating liquid, dip coating, spray coating, inkjet coating, roll coating, die coating, blade coating, curtain coating, wire bar coating, ring coating, etc. can be mentioned. Among these, dip coating is preferred from the viewpoint of efficiency and productivity.

[0038] Each layer will be described below. <First support> The first support is preferably a conductive support having electrical conductivity. The shape of the first support may be a cylinder, a belt, a sheet, or the like. Of these, a cylinder is preferable. A surface treatment layer may be provided on the surface of the first support by blasting or cutting.

[0039] The material of the first support is preferably metal, resin, glass, or the like. Examples of the metal include aluminum, iron, nickel, copper, gold, stainless steel, and alloys thereof. Among these, a support made of aluminum is preferable. Furthermore, the resin or glass may be made conductive by a process such as mixing with or coating with a conductive material.

[0040] The first support may be provided with a surface treatment layer by anodizing the surface of the first support in an acidic liquid containing an oxidizing agent. In this case, for example, an inorganic acid such as sulfuric acid or chromic acid or an organic acid such as oxalic acid or sulfonic acid can be used as an electrolyte for the anodizing treatment. Conditions such as applied voltage, current density, treatment temperature, and time can be selected according to the type of electrolyte and film thickness. In addition, the anodized surface treatment layer used in the electrophotographic photoreceptor of the present invention may be subjected to a sealing treatment after electrolysis. As a method for the sealing treatment, hot water treatment, steam treatment, or various sealing agents such as nickel acetate and nickel fluoride may be used, but it is preferable to use nickel acetate, which can efficiently seal fine pores.

[0041] In particular, a surface treatment layer formed by anodizing the surface of an aluminum first support under appropriate conditions is called an anodized layer, and by appropriately controlling the above-mentioned treatment conditions, it can be used as the bottom layer in the present invention. For example, by increasing the anodization time of the first support and increasing the resistance R of the anodized aluminum layer, OPC can be made smaller.

[0042] <First conductive layer> A conductive layer (hereinafter, the conductive layer of the photoreceptor is referred to as the "first conductive layer") may be provided on the first support. By providing the first conductive layer, scratches and irregularities on the surface of the first support can be concealed and light reflection on the surface of the first support can be controlled. The first conductive layer preferably contains conductive particles and a resin.

[0043] In particular, by controlling the selection of conductive particles and resin, their compounding ratio, the method of dispersing the conductive particles in the coating liquid for the first conductive layer, and the like, it can be used as the bottom layer of the present invention.

[0044] The conductive particles may be made of a material such as metal oxide, metal, or carbon black. Examples of metal oxides include zinc oxide, aluminum oxide, indium oxide, silicon oxide, zirconium oxide, tin oxide, titanium oxide, magnesium oxide, antimony oxide, bismuth oxide, etc. Examples of metals include aluminum, nickel, iron, nichrome, copper, zinc, silver, etc. Among these, it is preferable to use metal oxides as the conductive particles, and it is particularly preferable to use titanium oxide, tin oxide, or zinc oxide.

[0045] When a metal oxide is used as the conductive particles, the surface of the metal oxide may be treated with a silane coupling agent or the like, or the metal oxide may be doped with an element such as phosphorus or aluminum or an oxide thereof. Examples of the doped element or oxide thereof include phosphorus, aluminum, niobium, and tantalum.

[0046] By controlling the relative dielectric constant of the conductive particles by changing the surface treatment method of the conductive particles or the metal oxide used, the capacitance C of the first conductive layer is increased, thereby OPC can be made smaller.

[0047] The conductive particles may have a laminated structure having a core particle and a coating layer that covers the core particle. Examples of the core particle include titanium oxide, barium sulfate, zinc oxide, etc. Examples of the coating layer include metal oxides such as tin oxide and titanium oxide.

[0048] When a metal oxide is used as the conductive particles, the volume average particle size is preferably 1 nm or more and 500 nm or less, and more preferably 3 nm or more and 400 nm or less.

[0049] Examples of the resin include polyester resin, polycarbonate resin, polyvinyl acetal resin, acrylic resin, silicone resin, epoxy resin, melamine resin, polyurethane resin, phenol resin, and alkyd resin.

[0050] The first conductive layer may further contain silicone oil, resin particles, a masking agent such as titanium oxide, and the like.

[0051] The average thickness of the first conductive layer is preferably from 1 μm to 50 μm, and particularly preferably from 3 μm to 40 μm.

[0052] The first conductive layer can be formed by preparing a coating solution for the first conductive layer containing the above-mentioned materials and solvent, forming a coating film of this, and drying it. Examples of the solvent used in the coating solution include alcohol-based solvents, sulfoxide-based solvents, ketone-based solvents, ether-based solvents, ester-based solvents, and aromatic hydrocarbon-based solvents. Examples of the dispersion method for dispersing the conductive particles in the coating solution for the first conductive layer include methods using a paint shaker, a sand mill, a ball mill, and a liquid collision type high-speed disperser.

[0053] <Undercoat layer> An undercoat layer may be provided on the first support or the first conductive layer, which can improve adhesion between layers and provide a charge injection blocking function. The undercoat layer preferably contains a resin. Alternatively, the undercoat layer may be formed as a cured film by polymerizing a composition containing a monomer having a polymerizable functional group.

[0054] Examples of the resin include polyester resin, polycarbonate resin, polyvinyl acetal resin, acrylic resin, epoxy resin, melamine resin, polyurethane resin, phenol resin, polyvinyl phenol resin, alkyd resin, polyvinyl alcohol resin, polyethylene oxide resin, polypropylene oxide resin, polyamide resin, polyamic acid resin, polyimide resin, polyamideimide resin, and cellulose resin.

[0055] Examples of the polymerizable functional group contained in the monomer having a polymerizable functional group include an isocyanate group, a blocked isocyanate group, a methylol group, an alkylated methylol group, an epoxy group, a metal alkoxide group, a hydroxyl group, an amino group, a carboxyl group, a thiol group, a carboxylic anhydride group, and a carbon-carbon double bond group.

[0056] For the purpose of improving electrical properties, the undercoat layer may further contain an electron transporting material, a metal oxide, a metal, a conductive polymer, etc. Among these, it is preferable to use an electron transporting material or a metal oxide. Examples of the electron transport substance include a quinone compound, an imide compound, a benzimidazole compound, a cyclopentadienylidene compound, a fluorenone compound, a xanthone compound, a benzophenone compound, a cyanovinyl compound, an aryl halide compound, a silole compound, a boron-containing compound, etc. An electron transport substance having a polymerizable functional group may be used as the electron transport substance, and the undercoat layer may be formed as a cured film by copolymerizing the electron transport substance with a monomer having the polymerizable functional group. Examples of metal oxides include indium tin oxide, tin oxide, indium oxide, titanium oxide, zinc oxide, aluminum oxide, silicon dioxide, etc. Examples of metals include gold, silver, aluminum, etc. The undercoat layer may further contain an additive.

[0057] The average thickness of the undercoat layer is preferably from 0.1 μm to 50 μm, more preferably from 0.2 μm to 40 μm, and particularly preferably from 0.3 μm to 30 μm.

[0058] The undercoat layer can be formed by preparing a coating solution for the undercoat layer containing the above-mentioned materials and solvent, forming a coating film from the coating solution, and drying and / or curing the coating solution. Examples of the solvent used in the coating solution include alcohol-based solvents, ketone-based solvents, ether-based solvents, ester-based solvents, and aromatic hydrocarbon-based solvents.

[0059] <Photosensitive layer> The photosensitive layer of an electrophotographic photoreceptor is mainly classified into (1) a multi-layer type photosensitive layer and (2) a single-layer type photosensitive layer. (1) The multi-layer type photosensitive layer has a charge generation layer containing a charge generation material and a charge transport layer containing a charge transport material. (2) The single-layer type photosensitive layer has a photosensitive layer containing both a charge generation material and a charge transport material.

[0060] (1) Laminated photosensitive layer The laminated type photosensitive layer has a charge generating layer and a charge transport layer.

[0061] (1-1) Charge generation layer The charge generating layer preferably contains a charge generating material and a resin.

[0062] Examples of the charge generating material include azo pigments, perylene pigments, polycyclic quinone pigments, indigo pigments, and phthalocyanine pigments. Among these, azo pigments and phthalocyanine pigments are preferred. Among phthalocyanine pigments, oxytitanium phthalocyanine pigments, chlorogallium phthalocyanine pigments, and hydroxygallium phthalocyanine pigments are preferred. The content of the charge generating material in the charge generating layer is preferably from 40% by mass to 85% by mass, and more preferably from 60% by mass to 80% by mass, based on the total mass of the charge generating layer.

[0063] Examples of the resin include polyester resin, polycarbonate resin, polyvinyl acetal resin, polyvinyl butyral resin, acrylic resin, silicone resin, epoxy resin, melamine resin, polyurethane resin, phenol resin, polyvinyl alcohol resin, cellulose resin, polystyrene resin, polyvinyl acetate resin, polyvinyl chloride resin, etc. Among these, polyvinyl butyral resin is preferable.

[0064] The charge generating layer may further contain additives such as an antioxidant and an ultraviolet absorbing agent, etc. Specific examples of such additives include hindered phenol compounds, hindered amine compounds, sulfur compounds, phosphorus compounds, and benzophenone compounds.

[0065] The average thickness of the charge generating layer is preferably from 0.10 μm to 1.00 μm, and more preferably from 0.15 μm to 0.40 μm.

[0066] The charge generating layer can be formed by preparing a coating solution for the charge generating layer containing the above-mentioned materials and solvent, forming a coating film of this, and drying it. Examples of the solvent used in the coating solution include alcohol-based solvents, sulfoxide-based solvents, ketone-based solvents, ether-based solvents, ester-based solvents, and aromatic hydrocarbon-based solvents.

[0067] (1-2) Charge transport layer The charge transport layer preferably contains a charge transport material and a resin.

[0068] Examples of the charge transport material include polycyclic aromatic compounds, heterocyclic compounds, hydrazone compounds, styryl compounds, enamine compounds, benzidine compounds, triarylamine compounds, and resins having groups derived from these materials. Among these, triarylamine compounds and benzidine compounds are preferred. The content of the charge transport material in the charge transport layer is preferably from 25% by weight to 70% by weight, and more preferably from 30% by weight to 55% by weight, based on the total weight of the charge transport layer.

[0069] Examples of the resin include polyester resin, polycarbonate resin, acrylic resin, polystyrene resin, etc. Among these, polycarbonate resin and polyester resin are preferable. As the polyester resin, polyarylate resin is particularly preferable. The content ratio of the charge transport material to the resin is preferably from 4:10 to 20:10, and more preferably from 5:10 to 12:10, in terms of mass ratio.

[0070] The charge transport layer may also contain additives such as antioxidants, ultraviolet absorbers, plasticizers, leveling agents, slipping agents, and abrasion resistance improvers. Specific examples of such additives include hindered phenol compounds, hindered amine compounds, sulfur compounds, phosphorus compounds, benzophenone compounds, siloxane-modified resins, silicone oils, fluororesin particles, polystyrene resin particles, polyethylene resin particles, silica particles, alumina particles, and boron nitride particles.

[0071] The average thickness of the charge transport layer is preferably from 5 μm to 50 μm, more preferably from 8 μm to 40 μm, and particularly preferably from 10 μm to 30 μm.

[0072] The charge transport layer can be formed by preparing a coating solution for the charge transport layer containing the above-mentioned materials and solvent, forming a coating film of this, and drying it. Examples of the solvent used in the coating solution include alcohol-based solvents, ketone-based solvents, ether-based solvents, ester-based solvents, and aromatic hydrocarbon-based solvents. Among these solvents, ether-based solvents or aromatic hydrocarbon-based solvents are preferred.

[0073] (2) Single-layer photosensitive layer The single-layer type photosensitive layer can be formed by preparing a coating solution for the photosensitive layer containing a charge generating material, a charge transporting material, a resin and a solvent, forming a coating film of this, and drying it. The charge generating material, the charge transporting material and the resin are the same as the examples of materials in "(1) Multi-layer type photosensitive layer" above.

[0074] <Protective layer> In the present invention, a protective layer may be provided on the photosensitive layer. By providing the protective layer, durability can be improved.

[0075] The protective layer preferably contains conductive particles and / or a charge transport material, and a resin. The conductive particles include particles of metal oxides such as titanium oxide, zinc oxide, tin oxide, and indium oxide. Examples of the charge transport material include polycyclic aromatic compounds, heterocyclic compounds, hydrazone compounds, styryl compounds, enamine compounds, benzidine compounds, triarylamine compounds, and resins having groups derived from these materials. Among these, triarylamine compounds and benzidine compounds are preferred. Examples of the resin include polyester, acrylic resin, phenoxy resin, polycarbonate, polystyrene, phenol resin, melamine resin, epoxy resin, etc. Among these, polycarbonate, polyester, and acrylic resin are preferable.

[0076] The protective layer may be formed as a cured film by polymerizing a composition containing a monomer having a polymerizable functional group. Examples of the reaction include thermal polymerization, photopolymerization, and radiation polymerization. Examples of the polymerizable functional group of the monomer having a polymerizable functional group include an acrylic group and a methacrylic group. A material having a charge transport function may be used as the monomer having a polymerizable functional group.

[0077] The protective layer may contain additives such as antioxidants, ultraviolet absorbers, plasticizers, leveling agents, slipping agents, abrasion resistance improvers, etc. Specific examples of such additives include hindered phenol compounds, hindered amine compounds, sulfur compounds, phosphorus compounds, benzophenone compounds, siloxane-modified resins, silicone oils, fluororesin particles, polystyrene resin particles, polyethylene resin particles, silica particles, alumina particles, and boron nitride particles.

[0078] The average thickness of the protective layer is preferably from 0.5 μm to 10 μm, and more preferably from 1 μm to 7 μm.

[0079] The protective layer can be formed by preparing a coating solution for the protective layer containing the above-mentioned materials and solvent, forming a coating film from the coating solution, and drying and / or curing the coating solution. Examples of the solvent used in the coating solution include alcohol-based solvents, ketone-based solvents, ether-based solvents, sulfoxide-based solvents, ester-based solvents, and aromatic hydrocarbon-based solvents.

[0080] <Method for measuring impedance of the bottom layer> The impedance of the bottom layer can be measured by the following method. In order to eliminate the influence of contact resistance between the bottom layer and the measurement electrode when measuring impedance, there is a method in which a low-resistance thin film is deposited on the surface of the bottom layer, the thin film is used as an electrode, and the conductive first support is used as a ground electrode to measure impedance with two terminals. Methods for forming the thin film include metal deposition, sputtering, application of metal paste, and application of metal tape.

[0081] However, when electrodes are directly formed on a specific bottom layer by these methods, there is a concern that the electrodes or the solvent in which the electrodes are dispersed may contaminate the bottom layer. From this viewpoint, it is preferable to ground the surface of the bottom layer by a method of contacting a needle electrode. The needle electrode is connected to a measuring device, and the first support side is connected to the earth side of the measuring device. This allows the measuring device to conveniently acquire an electrical signal from the bottom layer, and allows impedance measurement to be performed.

[0082] Impedance measurement equipment includes impedance analyzers, network analyzers, spectrum analyzers, etc., and is used for 1.0×10 6 Any device capable of measuring impedance in a frequency band up to 300 Hz will suffice. Of these, it is preferable to use an impedance analyzer to measure the electrical resistance of the lowest layer.

[0083] The impedance measurement conditions are as follows. An impedance measuring device was used, and the impedance was measured at 1.0×10 -2 Hz~1.0×10 6 The impedance is measured in the frequency band of 100 Hz. The measurement is performed in an environment with a temperature of 23°C and a relative humidity of 50%, and it is preferable to set five or more measurement points per digit of frequency in order to reduce measurement variation.

[0084] Regarding the measurement voltage, a DC voltage may be applied while taking into consideration the voltage applied to the bottom layer in the electrophotographic device. Specifically, it is preferable to measure while applying a DC voltage of 10 V or less in combination with an oscillating voltage in order to quantify the characteristics of charge transport and accumulation.

[0085] In the embodiment of the present invention, a needle electrode with a diameter of 1 mm was attached to the tip of the high-voltage side conductor of an impedance measuring device (Solatron 1260 and Solartron 1296, Solartron), and this needle electrode was vertically abutted against the bottom layer, which had been exposed with an appropriate solvent or the like. A conductive clip was attached to the earth side conductor of the impedance device, and electrical continuity was achieved by clamping the exposed core material of the first support. If necessary, the surface of the first support was polished with a file to ensure sufficient electrical continuity. Measurements were taken while applying a DC voltage of -8 V superimposed with an AC voltage of 1 Vpp, and the frequency was 1.0 x 10 -2 Hz~1.0×10 6 Measurements were taken in Hz (10 points were measured when the frequency changed by one order of magnitude).

[0086] [Electrostatically charged materials] The charging member according to the present invention can be, for example, a charging roller having a second conductive layer.

[0087] The charging roller can be formed, for example, through a method including the following steps (1) to (4). Step (1): preparing a domain-forming rubber mixture (hereinafter also referred to as "CMB") containing an electronic conductive material and a second rubber. Step (2): preparing a matrix-forming rubber mixture (hereinafter also referred to as "MRC") containing a first rubber. Step (3): Kneading the CMB and the MRC to prepare a rubber mixture having a matrix-domain structure. Step (4): Forming a layer of the rubber mixture prepared in step (3) directly or through another layer on the surface of a second conductive support, and curing the layer of rubber mixture to form the second conductive layer of the present invention.

[0088] <Second support> The second support is preferably a conductive support having electrical conductivity. The shape of the second support may be a cylinder, a belt, a sheet, etc. Among these, a cylinder is preferable. The material of the second support is preferably metal, resin, glass, or the like. Examples of metals include aluminum, iron, nickel, copper, gold, stainless steel, and alloys thereof. These may be subjected to oxidation treatment or plating treatment with chromium, nickel, etc. As the type of plating, either electric plating or electroless plating can be used, but electroless plating is preferred from the viewpoint of dimensional stability. Examples of the type of electroless plating used here include nickel plating, copper plating, gold plating, and various other alloy platings. The plating thickness is preferably 0.05 μm or more, and considering the balance between work efficiency and rust prevention ability, the plating thickness is preferably 0.1 to 30 μm. The cylindrical shape of the second support may be a solid cylindrical shape or a hollow cylindrical shape (cylindrical shape). The outer diameter of this second support is preferably in the range of 3 mm to 10 mm.

[0089] <Middle Class> An intermediate layer may be provided between the second support and the second conductive layer, which enhances the adhesion between the layers and allows the charge supply capability to be controlled. The intermediate layer is preferably a thin conductive resin layer such as a primer, from the viewpoint of quickly supplying charge after the charge is consumed by discharging during the charging process and stabilizing the charge. As the primer, a known one can be selected and used depending on the rubber material for forming the second conductive layer and the material of the second support, etc. Examples of the primer material include thermosetting resins and thermoplastic resins such as phenolic resins, urethane resins, acrylic resins, polyester resins, polyether resins, and epoxy resins.

[0090] <Second conductive layer> The second conductive layer is provided on the outer surface of the second support and has a matrix containing a first rubber and a plurality of domains dispersed in the matrix. The domains contain a second rubber and an electronic conductive agent, and the matrix has a volume resistivity ρ M is the volume resistivity ρ of the domain D 1.0 x 10 5 The volume resistivity ρ of the matrix is ​​ρ M and the volume resistivity ρ of the domain D By satisfying the above relationship, the function of temporarily suspending the charge at the interface between the matrix and the domain is realized. This allows an abundant accumulation of charge within the domain, and the large amount of accumulation improves the efficiency of charge transfer between the domains. In other words, the volume resistivity ρ D and the volume resistivity of the matrix ρ M When the difference between these two becomes large, the response in the conductive layer improves, and the reaction frequency shifts to the higher frequency side.

[0091] In order to clarify the charge contrast on the photoconductor corresponding to the sea-island structure, the volume resistivity ρ M is 1.0×10 12 It is preferable that the resistivity is 1.0 [Ω·cm] or more.

[0092] Matrix volume resistivity ρ M to 1.0×10 12 By setting the surface roughness at 0.05 mm or more, discharge and charge inflow from the matrix are significantly suppressed, and the discharge contrast in the discharge area during the charging process and the current contrast in the nip area are increased. As a result, the charge contrast on the photoconductor after the charging process, which corresponds to the sea-island structure of the charging roller, can be made clearer. In addition, C Impedance z per unit area of ​​the charged member at / 10[Hz] C is 1.0 × 10 6 [Ω cm 2 [Hz] or more.

[0093] The thickness of the conductive layer is not particularly limited as long as the desired functions and effects of the charging member are obtained, but it is preferably 1.0 mm or more and 4.5 mm or less.

[0094] <Method for measuring the impedance of charged members> The impedance of the charging member can be measured by the following method. When measuring impedance, in order to eliminate the effect of contact resistance between the charged member and the measurement electrode, a low-resistance thin film is deposited on the surface of the charged member and used as an electrode while a conductive second support is used as a ground electrode to measure the impedance via two terminals.

[0095] Examples of the method for forming the thin film include metal deposition, sputtering, application of a metal paste, application of a metal tape, etc. Among these, from the viewpoint of reducing the contact resistance with the conductive member, it is preferable to form the electrode by deposition of a metal thin film such as platinum or palladium.

[0096] When forming a thin metal film on the surface of a charged member, taking into consideration the simplicity of the process and the uniformity of the thin film, it is preferable to use a vacuum deposition apparatus that is equipped with a mechanism for gripping the charged member and that is further equipped with a rotation mechanism for a conductive member having a cylindrical cross section.

[0097] For a cylindrical charged member having a curved cross section such as a circle, it is difficult to connect the thin metal film as the measurement electrode to the impedance measuring device, so it is preferable to use the following method. Specifically, a thin metal film electrode with a width of about 10 mm to 20 mm is formed in the longitudinal direction of the charged member, and then a metal sheet is tightly wrapped around the charged member, and the metal sheet is connected to the measurement electrode protruding from the measuring device for measurement. This allows the measuring device to obtain an electrical signal from the second conductive layer of the charged member in an appropriate manner, and impedance measurement can be performed. The metal sheet may be any metal sheet that has an electrical resistance value equivalent to that of the metal part of the connecting cable of the measuring device when measuring impedance, and for example, aluminum foil, metal tape, etc. can be used.

[0098] The impedance measuring device is an impedance analyzer, a network analyzer, a spectrum analyzer, etc., and is 1.0 x 10 6 Any device capable of measuring impedance in a frequency band up to 100 Hz may be used. Among these, it is preferable to measure the impedance using an impedance analyzer in the range of the electrical resistance of the charging member.

[0099] The impedance was measured using an impedance measuring device at a value of 1.0 x 10 -2 Hz~1.0×10 6 The impedance is measured in the frequency band of 100 Hz. The measurement is performed in an environment with a temperature of 23°C and a relative humidity of 50%. In order to reduce measurement variation, it is preferable to set five or more measurement points per digit of frequency.

[0100] Regarding the measurement voltage, a DC voltage may be applied while taking into consideration the voltage applied to the charging member in the electrophotographic apparatus. Specifically, it is preferable to measure while applying a DC voltage of 10 V or less in combination with an oscillating voltage in order to quantify the characteristics of charge transport and accumulation.

[0101] In the embodiment of the present invention, first, as a pretreatment, a measurement electrode was created by vacuum-depositing platinum on the fabricated charged member while rotating it. At this time, a band-shaped electrode with a longitudinal width of 1.5 cm and uniformity in the circumferential direction was created using masking tape. By forming this electrode, the influence of the contact resistance between the measurement electrode and the conductive member due to the surface roughness of the conductive member can be eliminated as much as possible. Next, an aluminum sheet was tightly wrapped around the electrode to form the measurement electrode on the conductive member side.

[0102] A schematic diagram of the state in which the measurement electrodes are formed on the charging roller is shown in Fig. 10. In Fig. 10, 111 is a conductive second support, 112 is a second conductive layer having a matrix domain structure, 113 is a platinum vapor deposition layer, and 114 is an aluminum sheet.

[0103] Figure 11 shows a cross-sectional view of a charging roller with a measurement electrode formed thereon. 121 is a conductive second support, 122 is a second conductive layer with a matrix domain structure, 123 is a platinum vapor deposition layer, and 124 is an aluminum sheet. As shown in Figure 11, it is important to sandwich the second conductive layer with a matrix domain structure between the conductive second support and the measurement electrode.

[0104] A schematic diagram of this measurement system is shown in Fig. 12. The aluminum sheet 124 is connected to a measurement electrode on the side of an impedance measuring device 125 (for example, Solartron 1260 and Solartron 1296 manufactured by Solartron, etc.). Impedance measurement is performed by using the conductive second support 121 and the aluminum sheet 124 as two electrodes of the impedance measuring device 125 for measurement.

[0105] When measuring the impedance, the charged member is left in an environment of a temperature of 23° C. and a relative humidity of 50% for 48 hours to saturate the moisture content of the charged member. Impedance measurements were performed at a temperature of 23°C and a relative humidity of 50%, with an AC voltage of 1Vpp and a frequency of 1.0×10 -2 Hz~1.0×10 6 Measure in Hz (measure five points each time the frequency changes by one order of magnitude) to obtain the impedance measurement value.

[0106] <ρ D , ρ M , and a method for controlling the domain matrix structure> Regarding the second conductive layer of the present invention, the volume resistivity ρ of the domain D [Ω cm], matrix volume resistivity ρ M In order to control the resistivity [Ω·cm] and the domain matrix structure, the type and content of the materials used in each of the steps (1) to (4) of manufacturing the charging roller described above may be selected and the manufacturing conditions may be adjusted.

[0107] First, the volume resistivity ρ D can be controlled by the amount of electronic conductive agent in the CMB. For example, the oil absorption of dibutyl phthalate (DBP) as an electronic conductive agent is 40 [cm 3 ] / 100[g] or more, 170[cm] 3 ] / 100[g] or less. In this case, the CMB is prepared so that it contains 40 mass % or more and 200 mass % or less of conductive carbon black based on the total mass of the CMB, and the ρ D to 1.0×10 1 [Ω cm] or more 1.0×10 4 It is possible to control the density of the powder to less than [Ω·cm].

[0108] As the rubber material for the domains, a rubber composition containing a rubber component for the matrix can be used. From the viewpoint of facilitating the formation of a sea-island structure, the difference in SP value between the rubber material forming the matrix and the domains should be 0.4 [(J / cm 3 ) 0.5 ] or more, 5.0[(J / cm 3 ) 0.5 ] or less, and 0.4 [(J / cm 3 ) 0.5 ] or more, 2.2[(J / cm 3 ) 0.5 ] or less is more preferable.

[0109] The volume resistivity of the domain can be adjusted by appropriately selecting the type of electronic conductive agent and the amount of the electronic conductive agent added. Examples of the electronic conductive agent to be added to the domain include oxides such as carbon black, graphite, titanium oxide, and tin oxide, metals such as Cu and Ag, and particles that are coated with the oxides of these metals to make them conductive. If necessary, two or more of these conductive agents may be mixed in appropriate amounts and used.

[0110] Among the above electronic conductive agents, it is preferable to use conductive carbon black, which has a high affinity with rubber and allows easy control of the distance between the electronic conductive agents. Examples of carbon black to be blended into the domain include, but are not limited to, gas furnace black, oil furnace black, thermal black, lamp black, acetylene black, and ketjen black.

[0111] Among these, from the viewpoint of imparting high electrical conductivity to the domain, we selected 3 ] / 100[g] or more 170[cm 3 ] / 100[g] or less can be suitably used.

[0112] The conductive agent such as conductive carbon black is preferably blended in the domain in an amount of 20 parts by mass or more and 150 parts by mass or less per 100 parts by mass of the rubber component contained in the domain. A particularly preferred blending ratio is 50 parts by mass or more and 100 parts by mass or less. The blending ratio of the conductive agent in these ratios is preferably a larger amount of conductive agent than that in general electrophotographic charging members.

[0113] If necessary, fillers, processing aids, crosslinking aids, crosslinking accelerators, antiaging agents, crosslinking accelerators, crosslinking retarders, softeners, dispersants, colorants, and the like, which are generally used as compounding agents for rubber, may be added to the rubber composition for the domain within a range that does not impair the effects of the present invention.

[0114] Next, the volume resistivity ρ of the matrix Mcan be controlled by the composition of the MRC. For example, the first rubber used in the MRC may be natural rubber, butadiene rubber, butyl rubber, acrylonitrile butadiene rubber, urethane rubber, silicone rubber, fluororubber, isoprene rubber, chloroprene rubber, styrene-butadiene rubber, ethylene-propylene rubber, polynorbornene rubber, or the like, which have low electrical conductivity.

[0115] Furthermore, to the MRC, fillers, processing aids, crosslinking agents, crosslinking assistant agents, crosslinking accelerators, crosslinking accelerator assistant agents, crosslinking retarders, antiaging agents, softeners, dispersants, and colorants may be added as necessary. On the other hand, MRC has ρ M / ρ D ≧10 5 , and ρ M ≧1.0×10 12 In order to achieve this, it is preferable not to contain an electronic conductive agent such as carbon black.

[0116] Finally, the domain matrix structure can be effectively controlled by adjusting the following four factors (a) to (d). (a) Difference in interfacial tension σ between the CMB and the MRC. (b) Viscosity of CMB η D , and MRC viscosity η M Ratio of η D / η M . (c) Shear rate γ and shear energy E during kneading of CMB and MRC in the manufacturing process (3) of the charging roller DK . (d) The volume fraction of CMB relative to the MRC in the manufacturing process (3) of the charging roller.

[0117] Each step will be described below. (a) Interfacial tension difference between CMB and MRC Generally, when two types of incompatible rubber are mixed, phase separation occurs. This is because the interaction between the same polymers is stronger than the interaction between different polymers, so the same polymers aggregate together to reduce the free energy and stabilize. The interface of the phase-separated structure comes into contact with different polymers, so the free energy is higher than the interior, which is stabilized by the interaction between the same molecules. As a result, in order to reduce the free energy of the interface, interfacial tension is generated that tries to reduce the area of ​​contact with the different polymers. If this interfacial tension is small, the different polymers will tend to mix more uniformly in order to increase entropy. The state of uniform mixing is dissolution, and the solubility parameter (hereinafter referred to as the SP value), which is an indicator of solubility, tends to correlate with the interfacial tension.

[0118] In other words, the difference in interfacial tension σ between CMB and MRC is considered to correlate with the difference in the SP value of the rubber contained in each. The difference in absolute value of the SP value between the first rubber in MRC and the second rubber in CMB is 0.4 [(J / cm 3 ) 0.5 ] or more, 5.0[(J / cm 3 ) 0.5 ] or less, especially 0.4 [(J / cm 3 ) 0.5 ] or more than 2.2[(J / cm 3 ) 0.5 In this range, a stable phase separation structure can be formed, and the domain diameter of the CMB can be made small.

[0119] Specific examples of the second rubber that can be used in the CMB include natural rubber (NR), isoprene rubber (IR), butadiene rubber (BR), styrene-butadiene rubber (SBR), butyl rubber (IIR), ethylene-propylene rubber (EPM, EPDM), chloroprene rubber (CR), nitrile rubber (NBR), hydrogenated nitrile rubber (H-NBR), silicone rubber, and urethane rubber (U).

[0120] (b) Viscosity ratio of CMB to MRC Viscosity ratio η between CMB and MRCD / η M The closer to 1, the smaller the maximum Feret diameter of the domain can be. D / η M is 1.0≦η D / η M It is preferable that η is ≦2.0. D / η M The viscosity ratio can be adjusted by selecting the Mooney viscosity of the raw rubber used for CMB and MRC, and by mixing the type and amount of filler. It can also be adjusted by adding a plasticizer such as paraffin oil to the extent that it does not interfere with the formation of a phase separation structure. The viscosity ratio can also be adjusted by adjusting the temperature during kneading. The viscosity of the rubber mixture for forming the domain and the rubber mixture for forming the matrix can be obtained by measuring the Mooney viscosity ML(1+4) at the rubber temperature during kneading based on JIS K 6300-1:2013.

[0121] (c) Shear rate and energy during mixing of CMB and MRC The shear rate γ during mixing of CMB and MRC is faster, and the amount of energy during shear E DK The larger is, the smaller the interdomain distance can be.

[0122] γ can be increased by increasing the inner diameter of the stirring members such as the blades and screws of the kneader, decreasing the gap between the end face of the stirring member and the inner wall of the kneader, and increasing the rotation speed. DK This can be achieved by increasing the rotation speed of the stirring member and by increasing the viscosity of the second rubber in the CMB and the first rubber in the MRC.

[0123] (d) CMB volume fraction relative to MRC The volume fraction of the CMB relative to the MRC correlates with the probability of collision and merging between the CMBs. Specifically, when the volume fraction of the CMB relative to the MRC is reduced, the probability of collision and merging between the CMBs decreases. In other words, the interdomain distance can be reduced by reducing the volume fraction of the CMB relative to the MRC within a range where the required electrical conductivity can be obtained. From this viewpoint, it is preferable that the volume fraction of the CMB relative to the MRC is 15% or more and 40% or less.

[0124] Using the above method, ρ D and ρ M By controlling and forming an island structure, M / ρ D ≧1.0×10 5 , ρ M ≧1.0×10 12 It is possible to obtain a second conductive layer that satisfies the above.

[0125] <How to confirm the island structure> The presence of the sea-island structure in the second conductive layer can be confirmed by preparing a thin piece from the second conductive layer and closely observing the fracture surface formed in the thin piece.

[0126] Examples of the means for making a thin section include a sharp razor, a microtome, an FIB, etc. In order to observe the sea-island structure more accurately, the thin section for observation may be subjected to pretreatment such as staining or deposition to obtain a favorable contrast between the domain and the matrix.

[0127] The existence of the sea-island structure can be confirmed by observing the fracture surface of the formed and, if necessary, pretreated thin section using a laser microscope, a scanning electron microscope (SEM) or a transmission electron microscope (TEM). From the viewpoint of being able to easily and accurately confirm the sea-island structure, it is preferable to observe using a scanning electron microscope (SEM).

[0128] A slice of the second conductive layer is obtained by the above-mentioned method, and an image is obtained by observing the surface of the slice at 1,000 to 10,000 times magnification. Then, an image processing software (product name: ImageProPlus, manufactured by Media Cybernetics) or the like is used to convert the image to 8-bit grayscale and obtain a monochrome image with 256 gradations. Next, the image is inverted so that the domains in the fracture surface become white, and a binarization threshold is set for the brightness distribution of the image based on the algorithm of Otsu's discriminant analysis method to obtain a binarized image. Finally, the presence or absence of a matrix domain structure can be determined from the analysis image that has been image-processed to a state in which the domains and matrix are distinguished by binarization.

[0129] The presence of a sea-island structure in the second conductive layer can be confirmed when the analysis image includes a structure in which a plurality of domains 6b exist in an isolated state in a matrix 6a as shown in Fig. 2. The isolated state of the domains 6b may be such that each domain 6b is arranged in a state in which it is not connected to the other domains 6b, the matrix 6a is connected in the image, and the domains 6b are divided by the matrix 6a. Specifically, when an analysis region is a 50 [μm] square in the analysis image, the state in which the number of domains existing in an isolated state as described above is 80 percent or more of the total number of domains that do not contact the frame line of the analysis region is considered to have a sea-island structure.

[0130] The above-mentioned confirmation can be carried out by dividing the second conductive layer of the conductive member into 5 equal parts in the longitudinal direction and 4 equal parts in the circumferential direction, and then randomly selecting one point from each area to prepare slices at a total of 20 points, and then performing the above-mentioned measurements.

[0131] In an embodiment of the present invention, a slice was cut using a razor so that a cross section perpendicular to the longitudinal direction of the second conductive layer could be observed, platinum was evaporated, and then a scanning electron microscope (SEM) (product name: S-4800, manufactured by Hitachi High-Technologies) was used to photograph the slice at 1,000x magnification to obtain a cross-sectional image.

[0132] Next, in the embodiment of the present invention, the percentage K of the number of isolated domains 6b that are not connected to each other was calculated from the total number of domains 6b that exist within a 50 μm square region and do not have contacts with the frame line of the binary image using a counting function for the binary image obtained using the above image processing software and method. In this case, as shown in Figure 2, a group of domains 6b was confirmed in which a plurality of domains 6b are dispersed in a matrix 6a, and the domains 6b exist in an independent state without being connected to each other, while the matrix 6a is connected in the image.

[0133] Finally, in the examples of the present invention, the presence or absence of a sea-island structure was judged as follows: The second conductive layer was divided equally into 5 equal parts in the longitudinal direction and 4 equal parts in the circumferential direction, and slices were prepared at random points from each of the obtained regions, for a total of 20 points, and the above measurement was performed. If the arithmetic mean value K (number %) thus obtained was 80 or more, the sea-island structure was evaluated as "present," and if the arithmetic mean value K (number %) was less than 80, the sea-island structure was evaluated as "absent."

[0134] < Domain volume resistivity ρ D Measurement method> Domain volume resistivity ρ D can be measured by a microprobe after cutting the second conductive layer into a thin slice. Examples of the cutting method include a sharp razor, a microtome, and a focused ion beam method (FIB).

[0135] Regarding the preparation of the thin sections, it is necessary to eliminate the effect of the matrix and measure the volume resistivity of only the domains, so it is necessary to prepare thin sections with a thickness smaller than the interdomain distance previously measured with a scanning electron microscope (SEM) or transmission electron microscope (TEM), etc. Therefore, the preferred method of thinning is a method that can prepare very thin samples, such as a microtome.

[0136] The volume resistivity is measured by first grounding one side of the flake, and then identifying the locations of the matrix and domain in the flake. These locations can be identified by a means capable of measuring the volume resistivity or hardness distribution of the matrix and domain, such as a scanning probe microscope (SPM) or an atomic force microscope (AFM). Next, a probe is brought into contact with the matrix, and a DC voltage of 1 [V] is applied for 5 seconds to measure the arithmetic average value of the ground current value for 5 seconds, and the electrical resistance value is calculated by dividing the applied voltage by the measured value. Finally, the resistance value can be converted to volume resistivity using the film thickness of the flake. In this case, a means capable of shape measurement, such as an SPM or an AFM, is preferable because it can measure the film thickness of the flake at the same time as the resistance value.

[0137] ρ for a cylindrical charging member D The measurement can be performed by dividing the second conductive layer into four regions in the circumferential direction and five regions in the longitudinal direction, cutting out one thin slice sample from each of the regions, obtaining the above-mentioned measurements, and then calculating the arithmetic average value of the volume resistivity of a total of 20 samples.

[0138] In the examples, ultra-thin slices having a thickness of 1 μm were cut out from the second conductive layer using a microtome (product name: Leica EM FCS, manufactured by Leica Microsystems) at a cutting temperature of −100° C. When cutting the long thin slices, the direction of the cross section was set perpendicular to the longitudinal direction of the charging member, taking into account the direction in which the charge is transported for discharge.

[0139] Next, in the examples, in an environment of 23°C temperature and 50% relative humidity, the ultrathin section was placed on a metal plate, and a portion of the section that was in direct contact with the metal plate was selected. The portion corresponding to the domain was brought into contact with the cantilever of a scanning probe microscope (SPM) (product name: Q-Scope250, manufactured by Quesant Instrument Corporation). A voltage of 1 V was applied to the cantilever for 5 seconds, the current value was measured, and the arithmetic average value for 5 seconds was calculated.

[0140] Subsequently, in the examples of the present invention, the surface shape of the measurement section was observed with the SPM, and the thickness of the measurement location was calculated from the obtained height profile. Further, the concave area of the contact portion of the cantilever was calculated from the surface shape observation result. The volume resistivity was calculated from the thickness and the concave area.

[0141] Finally, in the examples of the present invention, the second conductive layer was divided into five equal parts in the longitudinal direction and four equal parts in the circumferential direction, and 20 such sections were produced by arbitrarily taking one point from each of the obtained regions, and the above measurements were performed. The average value was taken as the volume resistivity ρ of the domain D and used. In the examples of the present invention, the SPM was scanned in contact mode.

[0142] <The ρ of the volume resistivity of the matrix M Measurement method> The volume resistivity ρ of the matrix M The measurement of can be carried out in the same manner as the <measurement method of the volume resistivity ρ of the domain D except that the measurement location is changed to a location corresponding to the matrix and the applied voltage during the measurement of the current value is changed to 50V.

[0143] In the examples of the present invention, compared with the method in the examples of the present invention in the <measurement method of the volume resistivity ρ of the domain D except that the measurement location is changed to a location corresponding to the matrix and the applied voltage during the measurement of the current value is changed to 50V, it was carried out in the same manner.

[0144] <Measurement method of SP value> The SP value can be calculated with high accuracy by creating a calibration curve using a material with a known SP value. The known SP value can also be the catalog value of the material manufacturer. For example, the SP value of NBR and SBR is determined almost entirely by the content ratio of acrylonitrile and styrene, regardless of the molecular weight. Therefore, by using analytical methods such as pyrolysis gas chromatography (Py-GC) and solid-state NMR on the rubber constituting the matrix and domain, the content ratio of acrylonitrile or styrene can be analyzed, and the SP value can be calculated by combining with the calibration curve obtained from a material with a known SP value. In addition, the SP value of isoprene rubber is determined by the isomer structure, such as 1,2-polyisoprene, 1,3-polyisoprene, 3,4-polyisoprene, cis-1,4-polyisoprene, and trans-1,4-polyisoprene. Therefore, the SP value can be calculated by analyzing the isomer content ratio using Py-GC and solid-state NMR, as with SBR and NBR, and combining with the calibration curve obtained from a material with a known SP value. The SP values ​​of materials with known SP values ​​were determined by the Hansen sphere method.

[0145] [Process cartridges, electrophotographic devices] The process cartridge of the present invention is characterized in that it integrally supports the electrophotographic photosensitive member and the charging member described above and is detachably mountable to the main body of the electrophotographic apparatus. The process cartridge of the present invention may also integrally support at least one means selected from the group consisting of a developing means, a transfer means and a cleaning means.

[0146] The electrophotographic apparatus of the present invention is characterized in that it comprises an exposure means, a developing means and a transfer means in addition to the electrophotographic photosensitive member and the charging member described above.

[0147] The photoconductor and the charging member of the process cartridge of the present invention are OPC [Hz] and f of charged material C [Hz] relationship f OPC / f C satisfies the following formula (D3) or the following formula (D4). 30≦fOPC / f C ≦3,000 Formula (D3) 0.0003≦f OPC / f C ≦0.03 Formula (D4)

[0148] Furthermore, in order to suppress lateral movement by balancing the electrical resistance between the photoconductor and the charging member, f OPC Impedance z per unit area of ​​the bottom layer at 10 [Hz] OPC [Ω cm 2 ] and f C Impedance z per unit area of ​​the charging member at 10 [Hz] C [Ω cm 2 ] preferably satisfies the relationship of the following formula (D5). (z OPC xz C ) ≧ 1.0 × 10 6 Formula (D5)

[0149] FIG. 1 shows an example of a schematic configuration of an electrophotographic apparatus having a process cartridge equipped with an electrophotographic photosensitive member and a charging member.

[0150] A cylindrical electrophotographic photoreceptor 1 is driven to rotate around an axis 2 at a predetermined peripheral speed in the direction of the arrow. The surface of the electrophotographic photoreceptor 1 is charged to a predetermined positive or negative potential by a charging member 3. As shown in FIG. 1, the charging member of the present invention is a roller charging type using a roller-type charging member. The charged surface of the electrophotographic photoreceptor 1 is irradiated with exposure light 4 from an exposure means (not shown), and an electrostatic latent image corresponding to the target image information is formed. The electrostatic latent image formed on the surface of the electrophotographic photoreceptor 1 is developed with toner contained in a developing means 5, and a toner image is formed on the surface of the electrophotographic photoreceptor 1. The toner image formed on the surface of the electrophotographic photoreceptor 1 is transferred to a transfer material 7 by a transfer means 6. The transfer material 7 to which the toner image has been transferred is transported to a fixing means 8, where the toner image is fixed, and the transfer material is printed out outside the electrophotographic device. The electrophotographic device may have a cleaning means 9 for removing deposits such as toner remaining on the surface of the electrophotographic photoreceptor 1 after transfer. Also, a so-called cleanerless system may be used in which deposits are removed by a developing means or the like without providing a separate cleaning means. The electrophotographic apparatus may have a charge eliminating mechanism that eliminates charge on the surface of the electrophotographic photoreceptor 1 by pre-exposure light 10 from a pre-exposure means (not shown). Also, in order to mount and remove the process cartridge 11 of the present invention to and from the main body of the electrophotographic apparatus, a guide means 12 such as a rail may be provided.

[0151] The electrophotographic photoreceptor can be used in laser beam printers, LED printers, copiers, facsimiles, and combination machines thereof. EXAMPLES

[0152] The present invention will be described in more detail below using examples and comparative examples. The present invention is not limited to the following examples without departing from the gist of the present invention. In the following description of the examples, "parts" are by mass unless otherwise specified.

[0153] The thickness of each layer of the electrophotographic photoreceptor in the examples and comparative examples was measured, except for the charge generating layer, by a method using an eddy current film thickness meter (product name: Fischerscope, manufactured by Fisher Instruments) or a method of converting the specific gravity from the mass per unit area. The film thickness of the charge generating layer was measured by converting the Macbeth density value of the photoreceptor using a calibration curve previously obtained from the Macbeth density value measured by pressing a spectrodensitometer (product name: X-Rite504 / 508, manufactured by X-Rite) against the surface of the photoreceptor and the film thickness measured by observing a cross-sectional SEM image.

[0154] <Manufacture of electrophotographic photoreceptor> The first support, the first conductive layer, the undercoat layer, the charge generating layer, and the charge transport layer were prepared by the following method to manufacture an electrophotographic photoreceptor. The combination of the surface treatment layer, the first conductive layer, and the undercoat layer in the manufactured photoreceptor is shown in Table 1.

[0155] <Preparation of the first support> An aluminum cylinder (JIS-A3003, aluminum alloy) having a diameter of φ24 mm and a length of 257 mm was obtained by hot extrusion. If necessary, a surface treatment layer was formed by the method described below to obtain a first support.

[0156] (Preparation of Surface Treatment Layer 1) The first support was subjected to cutting using a sintered diamond cutting tool. As a cleaning process, the cylinder was degreased, etched with 2 wt % sodium hydroxide solution for 1 minute, neutralized, and then washed with pure water. Next, anodization was performed for 10 minutes in a 14 wt% sulfuric acid solution at a DC voltage of 20 V to form an anodized film on the cylinder surface. After washing with water, the cylinder was immersed in a 0.8 wt% nickel acetate solution at a temperature of 72°C for 15 minutes for sealing treatment. After further washing with pure water and drying treatment, a surface treatment layer 1 was obtained.

[0157] (Preparation of Surface Treatment Layer 2) The first support was subjected to cutting using a sintered diamond cutting tool. As a cleaning process, the cylinder was degreased, etched with 2 wt % sodium hydroxide solution for 1 minute, neutralized, and then washed with pure water. Next, anodization was performed for 20 minutes in a 10 wt% sulfuric acid solution at a DC voltage of 15 V to form an anodized film on the cylinder surface. After washing with water, the cylinder was immersed in a 1 wt% nickel acetate solution at a temperature of 80° C. for 15 minutes to perform a sealing treatment. After further washing with pure water and drying, a surface treatment layer 2 was obtained.

[0158] (Preparation of Surface Treatment Layer 3) Surface treatment layer 3 was obtained in the same manner as surface treatment layer 2, except that the anodization time was changed to 30 seconds.

[0159] (Preparation of Surface Treatment Layer 4) Surface treatment layer 4 was obtained in the same manner as for producing surface treatment layer 2, except that the anodization time was changed to 20 seconds.

[0160] (Preparation of Surface Treatment Layer 5) Surface treatment layer 5 was obtained in the same manner as for producing surface treatment layer 2, except that the anodization time was changed to 10 seconds.

[0161] <Preparation of the first conductive layer> (Conductive layer 1-1) 60 parts of barium sulfate particles coated with tin oxide (trade name: Pastran PC1, manufactured by Mitsui Mining & Smelting Co., Ltd.), 15 parts of titanium oxide particles (trade name: TITANIX JR, manufactured by Teika Co., Ltd.), 43 parts of resol-type phenolic resin (trade name: Phenolite J-325, manufactured by DIC, solid content 70% by mass), 0.015 parts of silicone oil (trade name: SH28PA, manufactured by Toray Dow Corning Co., Ltd.), 3.6 parts of silicone resin particles (trade name: Tospearl 120, manufactured by Momentive Performance Materials Japan LLC), 50 parts of 2-methoxy-1-propanol, and 50 parts of methanol were placed in a ball mill and dispersed for 20 hours to prepare a first conductive layer coating solution 1. The first conductive layer coating solution 1 was applied by dip coating onto the above-mentioned first support to form a coating film, and the coating film was heated at a temperature of 145°C for 1 hour to harden, thereby forming a conductive layer 1-1 having a film thickness of 25 μm.

[0162] (Conductive layer 1-2) Zinc oxide particles (average primary particle size: 50 nm, specific surface area: 19 m 2 / g, powder resistance: 4.7×10 6 100 parts of N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane (product name: KBM602, manufactured by Shin-Etsu Chemical) was added as a surface treatment agent to the mixture, and the mixture was stirred for 4 hours. The toluene was then distilled off under reduced pressure, and the mixture was dried at a temperature of 130°C for 4 hours to obtain surface-treated zinc oxide particles.

[0163] 100 parts of titanium oxide particles (trade name: JR-405, manufactured by Teika Co., Ltd., average primary particle diameter: 210 nm) were mixed with 500 parts of toluene by stirring, and 0.75 parts of N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane was added and stirred for 2 hours. After that, the toluene was distilled off by reduced pressure distillation, and the mixture was baked at a temperature of 120°C for 3 hours to obtain surface-treated titanium oxide particles.

[0164] [ka] Next, 75 parts of the above-mentioned surface-treated zinc oxide particles, 16 parts of a blocked isocyanate compound represented by formula (A2) (trade name: Sumidur 3175, solid content: 75 mass%, manufactured by Sumitomo Bayer Urethane), 9 parts of a polyvinyl butyral resin (trade name: S-LEC BM-1, manufactured by Sekisui Chemical Co., Ltd.), 1 part of 2,3,4-trihydroxybenzophenone (manufactured by Tokyo Chemical Industry Co., Ltd.), and 8.65 parts of titanium oxide particles surface-treated for the purpose of preventing interference fringes were added to a mixed solvent of 60 parts of methyl ethyl ketone and 60 parts of cyclohexanone to prepare a dispersion liquid. The dispersion liquid was dispersed in a vertical sand mill using glass beads having an average particle size of 1.0 mm at a temperature of 23° C. and a rotation speed of 1,500 rpm for 3 hours. After the dispersion treatment, 5 parts of crosslinked polymethyl methacrylate particles (product name: SSX-103, average particle size: 3 μm, manufactured by Sekisui Chemical Co., Ltd.) and 0.01 parts of silicone oil (product name: SH28PA, manufactured by Toray Dow Corning Co., Ltd.) were added to the obtained dispersion and stirred to prepare a first conductive layer coating liquid 2. The first conductive layer coating liquid 2 was dip-coated onto the first support to form a coating film, and the coating film was heated at a temperature of 160° C. for 40 minutes and polymerized to form a conductive layer 1-2 having a thickness of 30 μm.

[0165] (Conductive layers 1-3) Oxygen-deficient tin oxide (SnO 2 ) coated with titanium dioxide (TiO 2214 parts of phenol resin (monomer / oligomer of phenol resin) as a binder material (trade name: Plyofen J-325, manufactured by Dainippon Ink & Chemicals, Inc., resin solid content: 60% by mass), and 98 parts of 1-methoxy-2-propanol as a solvent were placed in a sand mill using 450 parts of glass beads with a diameter of 0.8 mm, and dispersion treatment was performed under the conditions of rotation speed: 2000 rpm, dispersion treatment time: 4.5 hours, and cooling water temperature setting: 18°C ​​to obtain a dispersion liquid. The glass beads were removed from this dispersion liquid using a mesh (opening: 150 μm). Silicone resin particles (trade name: Tospearl 120, manufactured by Momentive Performance Materials, Inc., average particle size 2 μm) as a surface roughening agent were added to the dispersion liquid so that the amount was 10% by mass of the total mass of the metal oxide particles and binder material in the dispersion liquid after removing the glass beads. Furthermore, silicone oil (product name: SH28PA, manufactured by Dow Corning Toray Co., Ltd.) serving as a leveling agent was added to the dispersion so that the amount was 0.01% by mass relative to the total mass of the metal oxide particles and the binder material in the dispersion, followed by stirring to prepare a first conductive layer coating solution 3. This first conductive layer coating solution 3 was dip-coated onto the first support, and the resulting coating film was dried and thermally cured at a temperature of 150° C. for 30 minutes to form a conductive layer 1-3 having a film thickness of 30 μm.

[0166] (Conductive layers 1-4) The anatase type titanium dioxide core material can be produced by the known sulfuric acid method, in which a solution containing titanium sulfate and titanyl sulfate is heated and hydrolyzed to produce a metatitanic acid slurry, which is then dehydrated and fired.

[0167] The core particles used were anatase-type titanium oxide particles with an average primary particle size of 200 nm. 2 Converted to 33.7 parts of niobium, Nb 2 O 5A titanium niobium sulfate solution containing 2.9 parts of niobium in terms of carbon was prepared. 100 parts of core particles were dispersed in pure water to prepare a suspension of 1000 parts, which was then heated to a temperature of 60°C. The titanium niobium sulfate solution and 10 mol / L sodium hydroxide were added dropwise over 3 hours so that the pH of the suspension was 2 to 3. After the entire amount was added dropwise, the pH was adjusted to approximately neutral, and a coagulant was added to precipitate the solids. The supernatant was removed, filtered, washed, and dried at a temperature of 110°C to obtain an intermediate containing 0.1 wt% of organic matter derived from the coagulant in terms of carbon. This intermediate was calcined in nitrogen at a temperature of 750°C for 1 hour, and then calcined in air at a temperature of 450°C to produce titanium oxide particles 1. The obtained particles had an average particle size (average primary particle size) of 220 nm in the particle size measurement method using the above-mentioned scanning electron microscope.

[0168] Next, a phenolic resin (phenolic resin monomer / oligomer) (product name: Plyofen J-325, manufactured by DIC, resin solid content: 60%, density after curing: 1.3 g / cm) was used as a binding material. 3 80 parts of the methyl 2-propanol ester was dissolved in 60 parts of 1-methoxy-2-propanol as a solvent to obtain a solution. 100 parts of metal oxide particles 1 were added to this solution, which was then placed in a vertical sand mill using 200 parts of glass beads with an average particle size of 1.0 mm as a dispersion medium, and the resultant was subjected to dispersion treatment for 2 hours under conditions of a dispersion temperature of 23±3°C and a rotation speed of 1500 rpm (circumferential speed of 5.5 m / s) to obtain a dispersion. The glass beads were removed from this dispersion using a mesh. The dispersion from which the glass beads had been removed was pressure-filtered using PTFE filter paper (trade name: PF060, manufactured by Advantec Toyo). The pressure-filtered dispersion was supplemented with 0.015 parts of silicone oil (trade name: SH28 PAINT ADDITIVE, manufactured by Toray Dow Corning) as a leveling agent, and silicone resin particles (trade name: KMP-590, manufactured by Shin-Etsu Chemical Co., Ltd., average particle size: 2 μm, density: 1.3 g / cm) as a surface roughness imparting agent. 3 ) and stirred to prepare a first conductive layer coating solution 4. This first conductive layer coating solution 4 was dip-coated onto the above-mentioned first support to form a coating film, and the coating film was heated at a temperature of 145° C. for 1 hour to be cured, thereby forming a conductive layer 1-4 having a thickness of 25 μm.

[0169] <Preparation of Undercoat Layer> (Undercoat layer 1) An undercoat solution was prepared by dissolving 25 parts of N-methoxymethylated nylon 6 (trade name: Toresin EF-30T, manufactured by Nagase Chemtex) in 480 parts of a 2 / 1 mixed solution of methanol / n-butanol (heat dissolution at a temperature of 65° C.). The solution was then filtered through a membrane filter (trade name: FP-022, pore size: 0.22 μm, manufactured by Sumitomo Electric Industries) to prepare undercoat layer coating solution 1. This undercoat layer coating solution 1 was dip-coated on the first support or the first conductive layer, and the resulting coating film was dried to form an undercoat layer 1 having a film thickness of 0.8 μm.

[0170] (Undercoat layer 2) 100 parts of rutile-type titanium oxide particles (average primary particle size: 50 nm, manufactured by Teika) were mixed with 500 parts of toluene and stirred to obtain a compound represented by formula (A3), where n=1, R 1 3.0 parts of ethyltrimethoxysilane, in which the aryl group is a methyl group, was added and stirred for 8 hours. Thereafter, toluene was removed by distillation under reduced pressure, and the mixture was dried at a temperature of 120° C. for 3 hours to obtain rutile-type titanium oxide particles surface-treated with ethyltrimethoxysilane. [ka] A dispersion was prepared by adding 18 parts of the rutile-type titanium oxide particles surface-treated with the ethyltrimethoxysilane, 4.5 parts of N-methoxymethylated nylon (trade name: Torejin EF-30T, Nagase Chemtex), and 1.5 parts of copolymer nylon resin (trade name: Amilan CM8000, Toray) to a mixed solvent of 90 parts of methanol, 60 parts of 1-butanol, and 15 parts of dimethyl ketone acetone. The dispersion was dispersed for 5 hours in a vertical sand mill using glass beads with a diameter of 1.0 mm to prepare a coating solution 2 for an undercoat layer. The coating solution 2 for an undercoat layer was dip-coated on the first support or the first conductive layer, and the resulting coating film was dried to form an undercoat layer 2 having a thickness of 0.8 μm.

[0171] <Charge generation layer> 10 parts of crystalline titanyl phthalocyanine crystals (charge generating substance) having a strong peak at a Bragg angle 2θ of 27.2 ± 0.3° in CuKα characteristic X-ray diffraction, 5 parts of polyvinyl butyral (trade name: Esrec BX-1, manufactured by Sekisui Chemical Co., Ltd.), and 250 parts of cyclohexanone were placed in a sand mill using glass beads with a diameter of 0.8 mm, and dispersion treatment was performed under the condition of a dispersion treatment time of 3 hours. Next, 250 parts of ethyl acetate was added to prepare a coating solution for the charge generation layer. This coating solution for the charge generation layer was dip-coated on the first support, or on the first conductive layer, or on the undercoat layer, and the obtained coating film was dried at a temperature of 100 °C for 10 minutes to form a charge generation layer having a Macbeth density value of 0.95.

[0172] <Charge transport layer> 90 parts of a charge transport substance represented by formula (A4), 100 parts of a polyarylate resin having a repeating unit of formula (A5) as a binder resin, and 0.05 part of silicone oil (trade name: KF-96, manufactured by Shin-Etsu Silicone Co., Ltd.) as a leveling agent were mixed in a mixed solvent of 480 parts of tetrahydrofuran and 120 parts of toluene to prepare a coating solution for the charge transport layer. This coating solution for the charge transport layer was dip-coated on the charge generation layer, and the obtained coating film was dried at a temperature of 140 °C for 30 minutes to form a charge transport layer having a film thickness of 20 μm. [Chemical formula] [Chemical formula]

[0173] [Table 1]

[0174] [Manufacture of unvulcanized rubber mixture (CMB) for domain formation] [Manufacturing example of CMB1] 100 parts of butyl rubber (trade name: JSR Butyl 065, manufactured by JSR Corporation) as the raw rubber, 60 parts of carbon black (trade name: Tokablack #5500, manufactured by Tokai Carbon Co., Ltd.) as the electronic conductive agent, 5 parts of zinc oxide (trade name: Zinc Oxide Type 2, manufactured by Sakai Chemical Industry Co., Ltd.) as the vulcanization accelerator, and 2 parts of zinc stearate (trade name: SZ-2000, manufactured by Sakai Chemical Industry Co., Ltd.) as the processing aid were mixed using a 6-liter pressure kneader (trade name: TD6-15MDX, manufactured by Toshing) to produce CMB1. The mixing conditions were a filling rate of 70 vol%, a blade rotation speed of 30 rpm, and 20 minutes.

[0175] At this time, the SP value and Mooney viscosity of the raw rubber, and the Mooney viscosity of CMB1 were measured by the above-described method. The results are shown in Table 2 together with the respective material compositions of CMB1. Note that the material abbreviations of the raw rubber types in Table 2 are shown in Table 4, and the material abbreviations of the electronic conductive agents are shown in Table 5. Note that "parts by mass" in Table 2 means the parts by mass of the electronic conductive agent with respect to 100 parts of the raw rubber type.

[0176] <Manufacturing Examples of CMB2 to 8> In the manufacturing example of CMB1, CMB2 to 8 were manufactured in the same manner as the manufacturing example of CMB1, except that the raw rubber type and the electronic conductive agent were changed as shown in Table 2. Also, in the same manner as CMB1, the SP value and Mooney viscosity of the raw rubbers of CMB2 to 8, and the Mooney viscosity of CMB2 to 8 were measured. The results are shown in Table 2 together with the respective material compositions of CMB2 to 8. Also, the material abbreviations of the raw rubber types in Table 2 are shown in Table 4, and the material abbreviations of the electronic conductive agents are shown in Table 5.

[0177]

Table 2

[0178] [Manufacture of Rubber Mixture for Matrix Formation (MRC)] <Manufacturing Example of MRC1> 100 parts of styrene-butadiene rubber (trade name: T1000, manufactured by Asahi Kasei) as the raw rubber, 70 parts of calcium carbonate (trade name: Nanox #30, manufactured by Maruo Calcium Co., Ltd.) as the filler, 7 parts of zinc oxide (trade name: Zinc Oxide Type 2, manufactured by Sakai Chemical Industry Co., Ltd.) as the vulcanization accelerator, and 2.8 parts of zinc stearate (trade name: SZ-2000, manufactured by Sakai Chemical Industry Co., Ltd.) as the processing aid were mixed using a 6-liter pressure kneader (trade name: TD6-15MDX, manufactured by Toshin) to produce MRC1. The mixing conditions were a filling rate of 70 vol%, a blade rotation speed of 30 rpm, and 16 minutes.

[0179] At this time, the SP value and Mooney viscosity of the raw rubber, and the Mooney viscosity of MRC1 were measured by the above-mentioned method. The results are shown in Table 3 together with the material composition of MRC1. In addition, "parts by mass" in Table 3 means the parts by mass of the conductive agent with respect to 100 parts of the raw rubber type. Also, the material abbreviations of the raw rubber types in Table 3 are shown in Table 4.

[0180] <Manufacturing Examples of MRC2 to 7> In the manufacturing example of MRC1, MRC2 to 7 were manufactured in the same manner as the manufacturing example of MRC1 except that the type of raw rubber was changed as shown in Table 3. Also, in the same manner as the manufacturing example of MRC1, the SP value and Mooney viscosity of the raw rubber of MRC2 to 7, and the Mooney viscosity of MRC2 to 7 were measured. The results are shown in Table 3 together with the material composition of MRC2 to 7.

[0181]

Table 3

[0182]

Table 4

[0183] [Table 5]

[0184] <Manufacturing of electrostatically charged components> (Manufacturing example of charging roller 1) As a cylindrical second support, a round bar having a total length of 252 mm and an outer diameter of 6 mm and made of stainless steel (SUS304) with a surface that had been electroless nickel plated was prepared.

[0185] Next, 25 parts of CMB1 and 75 parts of MRC1 were mixed using a 6-liter pressure kneader (product name: TD6-15MDX, manufactured by Toshin) at a filling rate of 70 vol%, a blade rotation speed of 30 rpm, and for 16 minutes.

[0186] Next, 100 parts of the mixture of CMB1 and MRC1, 3 parts of sulfur (product name: SULFAX PMC, manufactured by Tsurumi Chemical Industry Co., Ltd.) as a vulcanizing agent, and 3 parts of tetramethylthiuram disulfide (product name: Noccela TT-P, manufactured by Ouchi Shinko Chemical Co., Ltd.) as a vulcanizing aid were mixed using an open roll with a roll diameter of 12 inches to prepare an unvulcanized rubber mixture for forming the second conductive layer. The mixing conditions were a front roll rotation speed of 10 rpm, a rear roll rotation speed of 8 rpm, a roll gap of 2 mm, and a total of 20 left and right turns, followed by 10 thin passes with a roll gap of 0.5 mm.

[0187] Next, an unvulcanized rubber roller was manufactured using the device shown in Fig. 13. A die with an inner diameter of 10 mm was attached to the tip of the extruder of the crosshead 163 having a supply mechanism 164 for the second support 161 and a discharge mechanism for the unvulcanized rubber roller, and the temperature of the extruder 162 and the crosshead 163 was adjusted to 80°C, and the conveying speed of the second support 161 was adjusted to 60 mm / sec. Under these conditions, the unvulcanized rubber mixture for forming the second conductive layer was supplied from the extruder 162, and the outer periphery of the second support 161 was covered with the unvulcanized rubber mixture for forming the second conductive layer in the crosshead 163, to obtain an unvulcanized rubber roller 165.

[0188] Next, unvulcanized rubber roller 165 was placed in a hot air vulcanizing furnace at a temperature of 160°C and heated for 60 minutes to vulcanize the unvulcanized rubber mixture for forming a second conductive layer, thereby forming a second conductive layer on the outer periphery of second support 161. Thereafter, 10 mm was cut off from each of both ends of the second conductive layer to set the longitudinal length of the second conductive layer portion to 232 mm, thereby obtaining roller 166.

[0189] Finally, the surface of the second conductive layer of the roller 166 was ground with a rotary grindstone. This produced a charging roller 1 having a crown shape with a diameter of 8.4 mm at positions 90 mm from the center to both ends and a central diameter of 8.5 mm.

[0190] The volume resistivity ρ of the domain of the charging roller 1 obtained at this time D [Ω cm], matrix volume resistivity ρ M The results are shown in Table 6 along with the configuration of the charging roller 1. The abbreviations for the vulcanizing agents and vulcanization accelerators in Table 6 are shown in Table 7.

[0191] (Manufacturing Examples of Charging Rollers 2 to 15) Charge rollers 2 to 15 were manufactured in the same manner as in the manufacturing example of charge roller 1, except that the CMB, MRC, the mixing ratio of CMB and MRC, and the vulcanization accelerator were changed as shown in Table 6. Similarly to the charging roller 1, the volume resistivity ρ D [Ω cm], matrix volume resistivity ρ M The results are shown in Table 6 along with the configurations of charging rollers 2 to 15.

[0192] [Table 6]

[0193] [Table 7]

[0194] [Example 1] The photoreceptor 1 and the charging member 1 were mounted in a process cartridge of a laser beam printer (product name: Color Laser Jet Enterprise M653dn) manufactured by Hewlett-Packard Company, and the process cartridge of Example 1 was prepared. At this time, the f of the photoconductor 1 used OPC and z OPC The measured value of f of the charged member 1 C and z C The measured values ​​of and ρ M / ρ D The calculated value of f when the photoconductor 1 and the charging member 1 are combined OPC / f C and (z OPC xz C ) 0.5 The calculated values ​​are shown in Table 8.

[0195] [Examples 2 to 36, Comparative Examples 1 to 6] In Example 1, except that the photoconductor 1 and the charging member 1 were changed as shown in Table 8, the process cartridges of Examples 2 to 36 and Comparative Examples 1 to 6 were prepared in the same manner as in Example 1. In addition, the f OPC and z OPC The measured value of f of the charged member C and z C The measured values ​​of and ρ M / ρ D The calculated value of f when the photoconductor and charging member are combined OPC / f C and (z OPC xz C ) 0.5 The calculated values ​​are shown in Table 8.

[0196] [Table 8]

[0197] [evaluation] The process cartridges of the examples and comparative examples were evaluated as follows.

[0198] <Evaluation device> A Hewlett-Packard laser beam printer (product name: Color Laser Jet Enterprise M653dn) was prepared as the electrophotographic device for evaluation. The motor that rotates the photosensitive drum and other components was modified to 80 rpm, and the device was further modified so that the voltage applied to the charging roller, and the pre-exposure amount and image exposure amount to the photosensitive body could be adjusted and measured. Three process cartridges each of the examples and comparative examples were prepared. These process cartridges were installed only in the magenta process cartridge station, so that they could be operated without installing process cartridges for the other colors (cyan, yellow, black) in the laser beam printer body. When outputting an image, only the magenta process cartridge was attached to the laser beam printer body, and a monochromatic image was output using only magenta toner.

[0199] <Sideways> First, two photoconductors were removed from the process cartridge. A rotating drill was inserted perpendicularly into the center of the surface of the photoconductor, and holes of 2 mm in diameter were drilled until the undercoat layer was exposed. Five holes were drilled for each photoconductor, shifted in the circumferential direction of the photoconductor, so that there were no multiple holes on the same axis in the longitudinal direction of the photoconductor. A lateral running test was performed using the photoconductor and charging member 1 as follows.

[0200] FIG. 14 shows a leak test device. The lateral running test is performed in a high temperature and high humidity environment (temperature 30° C. / relative humidity 80%). Both ends of the electrophotographic photoreceptor 21 are placed on the fixing table 23 and fixed so as not to move. The contact portion 24 of the electrophotographic photoreceptor 21 with the first support is connected to earth via a reference resistor 25 of 100 kΩ. Next, the charging member 26 is abutted at one end 5N so as to contact the center of the photosensitive layer 27 of the electrophotographic photoreceptor 21. A power source 28 for applying a voltage is connected to the charging member 26. The electrophotographic photoreceptor 21 can be rotated around an axis in the longitudinal direction by the contact portion 24 with the first support.

[0201] While rotating the electrophotographic photoreceptor 21 at a rotation speed of 200 rpm, a voltage of -1500 V was applied to the charging member 26. In this case, in the current profile flowing from the electrophotographic photoreceptor 21 to the earth, the current that rushed into the portion where the undercoat layer was exposed (the portion where the current was detected to be larger than other portions) was taken as the lateral current. The measurement results of the lateral current at this time are shown in Table 9.

[0202] Next, a process cartridge using a photoconductor with holes was prepared again for each example and comparative example, and each process cartridge was attached to the evaluation machine. The voltage applied to the charging roller and the image exposure amount to the photoconductor were set so that the dark area potential was -750V and the light area potential was -130V. The pre-exposure amount was three times the image exposure amount. To measure the surface potential of the photoconductor when setting the potential, a potential probe (product name: model 6000B-8, manufactured by Trek Japan) was attached to the development position of the process cartridge, and a surface potential meter (product name: model 344, manufactured by Trek Japan) was used.

[0203] Using the same voltage applied to the charging roller and the same amount of pre-exposure and image exposure to the electrophotographic photosensitive member as above, a halftone image of a one-dot knight pattern was output on 10,000 sheets.

[0204] In the present invention, the image results corresponding to the five perforated portions in the halftone image output on the 10,000th sheet were ranked according to the following criteria. The evaluation criteria A to D were deemed to represent the effects of the present invention. The evaluation results are shown in Table 9. A: Only sunspots are observed in all five locations. B: Short, thin horizontal black streaks are observed in one or two out of five locations. C: Short, thin horizontal black streaks are observed in three or more of the five locations. D: One or two long horizontal black streaks spanning the entire image area are observed in five locations. E: Long horizontal black streaks spanning the entire image area are observed in three or more of five locations.

[0205] <Variation of electric potential> First, the process cartridges of the examples and comparative examples were prepared again, and the process cartridges and the electrophotographic device were left in a low temperature and low humidity environment (L / L: temperature 15°C / relative humidity 20%) for more than 24 hours, and then the process cartridges were attached to the magenta process cartridge station of the electrophotographic device.

[0206] The voltage applied to the charging roller and the image exposure to the photoconductor were set so that the dark potential was -750 V and the light potential was -130 V. The pre-exposure was three times the image exposure. To measure the surface potential of the photoconductor when setting the potential, a potential probe (product name: model 6000B-8, manufactured by Trek Japan) was attached to the development position of the process cartridge, and the measurement was performed using a surface potential meter (product name: model 344, manufactured by Trek Japan).

[0207] The process cartridge and the electrophotographic device were left in a low temperature and low humidity (L / L: temperature 15°C / relative humidity 20%) environment for 24 hours or more, and then the process cartridge was attached to the magenta process cartridge station of the electrophotographic device. The voltage applied to the charging roller and the image exposure amount to the photoconductor were set so that the dark area potential was -750V and the light area potential was -130V. The pre-exposure amount was three times the image exposure amount. Using this process cartridge and the electrophotographic device, a print operation was performed in an intermittent mode in which a character image with a print rate of 2% was output one sheet at a time on A4 size plain paper, and a paper feed durability test was performed by outputting 10,000 sheets of images.

[0208] Next, immediately after the 10,000-sheet paper-passing durability test, the applied voltage was set again so that the dark potential was -750 V. The applied voltage to the charging roller and the image exposure to the photoconductor were set so that the dark potential was -750 V and the light potential was -130 V, and the dark potential and the light potential were measured with the pre-exposure amount set to three times the image exposure amount. The measured light potential was V L [V], and the potential change before and after the 10,000-sheet paper feed durability test is ΔV L =|V L I asked for +130|.

[0209] In the present invention, ΔV L The results were ranked according to the following criteria, depending on the value of A. The evaluation criteria A to D were deemed to represent the effects of the present invention. The evaluation results are shown in Table 9. A: ΔV L <= 15 B:15<ΔV L <= 25 C:25<ΔV L <=35 D:35<ΔV L <= 45 E:45<ΔV L

[0210] [Table 9] [Explanation of symbols]

[0211] 1. Electrophotographic photoreceptor 2-axis 3. Charging materials 4 Exposure light 5. Developing method 6 Transfer Method 7 Transfer material 8 Fixing Method 9 Cleaning Method 10 Pre-exposure light 11 Process cartridge 12 Guidance means 6a Matrix 6b Domain 6c conductive particles 81 Electrostatic materials 111 Second support 112 Second conductive layer 113 Platinum vapor deposition layer 114 Aluminum Sheet 121 Second support 122 Second conductive layer 123 Platinum vapor deposition layer 124 Aluminum Sheet 125 Impedance Measuring Device 161 Conductive core 162 Extruder 163 2-layer crosshead 164 Core feed roller 165 Unvulcanized rubber roller 166 Lola 21 Electrophotographic photoreceptor 23 Fixed base 24 Part in contact with support 25 Reference Resistor 26 Step core bar 27 Photosensitive layer 28 Power supply

Claims

1. A process cartridge having an electrophotographic photosensitive member and a charging member, and being detachably mountable to a main body of an electrophotographic apparatus, The electrophotographic photoreceptor has a cylindrical first support, a bottom layer formed directly on the first support, and a photosensitive layer formed on the bottom layer, A needle electrode with a diameter of 1 mm connected to the high voltage side of an impedance measuring device was placed in contact with the bottom layer, and the earth side lead of the impedance measuring device was connected to the first support. A DC voltage of −8 V and an AC voltage with an amplitude of 1 Vpp and a frequency of 1.0×10 -2 [Hz]-1.0×10 6 When the impedance is measured while changing the frequency between f [Hz], the maximum frequency at which the phase of the impedance is 45° is defined as f OPC [Hz], The charging member is an electrophotographic charging member having a cylindrical second support and a second conductive layer formed on the second support, the second conductive layer has a matrix including a first rubber and a plurality of domains dispersed in the matrix; the domain comprises a second rubber and an electronic conductive agent; The volume resistivity ρ of the matrix M is the volume resistivity ρ of the domain D 1.0 x 10 5 More than double that. A strip-shaped metal thin film electrode having a longitudinal width of 1.5 cm was provided in the circumferential direction on the surface of the charging member, the metal thin film electrode was connected to one end of an impedance measuring device, the second support was connected to the other end of the impedance measuring device, and an AC voltage having an amplitude of 1 Vpp and a frequency of 1.0×10 -2 [Hz]-1.0×10 6 When the impedance is measured while changing the frequency between f [Hz], the maximum frequency at which the phase of the impedance is 45° is defined as f C When set to [Hz], f OPC and C A process cartridge characterized in that the relationship of the following formula (D1) or the following formula (D2) is satisfied: 10≦f OPC / f C ≦10,000 Type (D1) 0.0001≦f OPC / f C ≦0.1 Formula (D2).

2. In the electrophotographic photoreceptor and the charging member, OPC and the f C 2. The process cartridge according to claim 1, wherein the relationship of the following formula (D3) or the following formula (D4) is satisfied: 30 ≤ f OPC / f C ≤ 3,000 Formula (D3) 0.0003≦f OPC / f C ≦0.03 formula (D4).

3. In the electrophotographic photoreceptor, OPC 3. The process cartridge according to claim 1, wherein the frequency is 5 Hz or more.

4. In the electrophotographic photoreceptor, OPC 4. The process cartridge according to claim 1, wherein the rotational speed is 100 Hz or more.

5. A needle electrode having a diameter of 1 mm connected to a high voltage side of an impedance measuring device is brought into contact with the bottom layer of the electrophotographic photosensitive member, and a conductor on the earth side of the impedance measuring device is connected to the first support, and an AC voltage with an amplitude of 1 Vpp is applied to the surface of the first support and a DC voltage of -8 V while changing the frequency between 1.0 x 10-2 [Hz] and 1.0 x 106 [Hz], so that a measurement is performed at a frequency of f OPC When the impedance per unit area of ​​the bottom layer is measured at 10 [Hz], the measured value is z OPC [Ω cm 2 ]year, A strip-shaped metal thin film electrode having a longitudinal width of 1.5 cm was provided in the circumferential direction on the surface of the charging member, the metal thin film electrode was connected to one end of an impedance measuring device, and the second support was connected to the other end of the impedance measuring device. An AC voltage with an amplitude of 1 Vpp was applied while changing the frequency between 1.0×10 −2 [Hz] and 1.0×10 6 [Hz], and the frequency f C When the impedance per unit area of ​​the charging member is measured at 10 [Hz], the measured value is z C [Ω cm 2 ], Z OPC and z C The process cartridge according to any one of claims 1 to 4, wherein the relationship of the following formula (D5) is satisfied: (z OPC × C )≧1.0×10 6 Formula (D5).

6. A needle electrode having a diameter of 1 mm connected to a high voltage side of an impedance measuring device is brought into contact with the bottom layer of the electrophotographic photosensitive member, and a conductor on the earth side of the impedance measuring device is connected to the first support, and an AC voltage with an amplitude of 1 Vpp is applied to the surface of the first support and a DC voltage of -8 V while changing the frequency between 1.0 x 10-2 [Hz] and 1.0 x 106 [Hz], so that a measurement is performed at a frequency of f OPC When the impedance per unit area of ​​the bottom layer is measured at 10 [Hz], the measured value z OPC is 3.0 x 10 5 [Ω cm 2 6. The process cartridge according to claim 1, wherein the total mass of the ink-receiving layer is equal to or greater than 100 μm.

7. A needle electrode having a diameter of 1 mm connected to a high voltage side of an impedance measuring device is brought into contact with the bottom layer of the electrophotographic photosensitive member, and a lead on the earth side of the impedance measuring device is connected to the first support, and an AC voltage with an amplitude of 1 Vpp is applied to the surface of the first support and a DC voltage of -8 V is applied while changing the frequency between 1.0 x 10-2 [Hz] and 1.0 x 106 [Hz], so that a measurement is performed at a frequency of f OPC When the impedance per unit area of ​​the bottom layer is measured at 10 [Hz], the measured value z OPC is 1.0 x 10 9 [Ω cm 2 7. The process cartridge according to claim 1, wherein the total mass of the ink-receiving layer is equal to or less than 100 μm.

8. A strip-shaped metal thin film electrode having a longitudinal width of 1.5 cm is provided in the circumferential direction on the surface of the charged member, the metal thin film electrode is connected to one side of an impedance measuring device, the second support is connected to the other side of the impedance measuring device, and an AC voltage having an amplitude of 1 Vpp is applied while changing the frequency between 1.0 × 10 -2 [Hz] and 1.0 × 10 6 [Hz], and a measurement is performed at a frequency of f C When the impedance per unit area of ​​the charging member is measured at 10 [Hz], the measured value z C is 1.0 x 10 6 8. The process cartridge according to claim 1, wherein the surface tension is [Ω·cm 2 ] or more.

9. In the charging member, the volume resistivity ρ of the matrix M is 1.0 x 10 12 9. The process cartridge according to claim 1, wherein the resistivity is Ω·cm or more.

10. An electrophotographic apparatus having an electrophotographic photoreceptor and a charging member, The electrophotographic photoreceptor has a cylindrical first support, a bottom layer formed directly on the first support, and a photosensitive layer formed on the bottom layer, A needle electrode with a diameter of 1 mm connected to the high voltage side of an impedance measuring device was placed in contact with the bottom layer, and the exposed core material of the first support was connected to the earth side of the impedance measuring device. A DC voltage of −8 V and an AC voltage with an amplitude of 1 Vpp and a frequency of 1.0×10 were applied to the surface of the first support. -2 [Hz]-1.0×10 6 When the impedance is measured while changing the frequency between f [Hz], the maximum frequency at which the phase of the impedance is 45° is defined as f OPC [Hz], The charging member is an electrophotographic charging member having a cylindrical second support and a second conductive layer formed on the second support, the second conductive layer has a matrix including a first rubber and a plurality of domains dispersed in the matrix; the domain comprises a second rubber and an electronic conductive agent; The volume resistivity ρ of the matrix M is the volume resistivity ρ of the domain D 1.0 x 10 5 More than double that. A thin metal film electrode is provided on the surface of the charged member, a metal sheet is wrapped around the thin metal film electrode, the metal sheet is connected to the high-voltage side electrode of an impedance measuring device, the second support is connected to the earth side of the impedance measuring device, and an AC voltage having an amplitude of 1 Vpp and a frequency of 1.0×10 -2 [Hz]-1.0×10 6 When the impedance is measured while changing the frequency between f C [Hz], the maximum frequency at which the phase of the impedance is 45° is f C [Hz]. f OPC and C satisfies the relationship of the following formula (D1) or the following formula (D2): 10≦f OPC / f C ≦10,000 Type (D1) 0.0001≦f OPC / f C ≦0.1 Formula (D2).

Citation Information

Patent Citations

  • Electrophotographic photoreceptor

    JP1998268541A

  • Semiconductive rubber composition, electrified member, electrophotographic device and process cartridge

    JP2002003651A

  • Charging apparatus and image forming apparatus

    JP2007078872A

  • Electrophotographic photoreceptor, process cartridge, and image forming apparatus

    JP2016139052A